3D convolutional neural network-based autosegmentation improves brain metastases detection and quantification for brain stereotactic radiotherapy treatment planning - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmidt, Manuel; Heiß, Rafael; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

7 tricks for 7 T CEST: Improving the reproducibility of multipool evaluation provides insights into the effects of age and the early stages of Parkinson's disease - Mennecke, Angelika; Khakzar, Katrin M.; German, Alexander; Herz, Kai; Fabian, Moritz; Liebert, Andrzej; Blümcke, Ingmar; Kasper, Burkhard; Nagel, Armin Michael; Laun, Frederik Bernd; Schmidt, Manuel; Winkler, Jürgen; et al. (NMR in Biomedicine, 2022)
The objective of the current study was to optimize the postprocessing pipeline of 7 T chemical exchange saturation transfer (CEST) imaging for reproducibility and to prove this optimization for the detection of age differences and differences between patients with Parkinson's disease versus normal subjects. The following 7 T CEST MRI experiments were analyzed: repeated measurements of a healthy subject, subjects of two age cohorts (14 older, seven younger subjects), and measurements of 12 patients with Parkinson's disease. A slab-selective, (Formula presented.) -homogeneous parallel transmit protocol was used. The postprocessing, consisting of motion correction, smoothing, (Formula presented.) -correction, normalization, denoising, (Formula presented.) -correction and Lorentzian fitting, was optimized regarding the intrasubject and intersubject coefficient of variation (CoV) of the amplitudes of the amide pool and the aliphatic relayed nuclear Overhauser effect (rNOE) pool within the brain. Seven “tricks” for postprocessing accomplished an improvement of the mean voxel CoV of the amide pool and the aliphatic rNOE pool amplitudes of less than 5% and 3%, respectively. These postprocessing steps are: motion correction with interpolation of the motion of low-signal offsets (1) using the amide pool frequency offset image as reference (2), normalization of the Z-spectrum using the outermost saturated measurements (3), (Formula presented.) correction of the Z-spectrum with moderate spline smoothing (4), denoising using principal component analysis preserving the 11 highest intensity components (5), (Formula presented.) correction using a linear fit (6) and Lorentzian fitting using the five-pool fit model (7). With the optimized postprocessing pipeline, a significant age effect in the amide pool can be detected. Additionally, for the first time, an aliphatic rNOE contrast between subjects with Parkinson's disease and age-matched healthy controls in the substantia nigra is detected. We propose an optimized postprocessing pipeline for CEST multipool evaluation. It is shown that by the use of these seven “tricks”, the reproducibility and, thus, the statistical power of a CEST measurement, can be greatly improved and subtle changes can be detected.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 7 T; age; amide; CEST; Lorentzian fitting; Parkinson; rNOE; standardization

Accuracy of Dose-Saving Artificial-Intelligence-Based 3D Angiography (3DA) for Grading of Intracranial Artery Stenoses: Preliminary Findings - Lang, Stefan; Hölter, Philip; Schmidt, Manuel; Mrochen, Anne; Kuramatsu, Joji; Kaethner, Christian; Roser, Philipp; Kowarschik, Markus; Dörfler, Arnd (Diagnostics, 2023)
Background and purpose: Based on artificial intelligence (AI), 3D angiography (3DA) is a novel postprocessing algorithm for “DSA-like” 3D imaging of cerebral vasculature. Because 3DA requires neither mask runs nor digital subtraction as the current standard 3D-DSA does, it has the potential to cut the patient dose by 50%. The object was to evaluate 3DA’s diagnostic value for visualization of intracranial artery stenoses (IAS) compared to 3D-DSA. Materials and methods: 3D-DSA datasets of IAS (nIAS = 10) were postprocessed using conventional and prototype software (Siemens Healthineers AG, Erlangen, Germany). Matching reconstructions were assessed by two experienced neuroradiologists in consensus reading, considering image quality (IQ), vessel diameters (VD1/2), vessel-geometry index (VGI = VD1/VD2), and specific qualitative/quantitative parameters of IAS (e.g., location, visual IAS grading [low-/medium-/high-grade] and intra-/poststenotic diameters [dintra-/poststenotic in mm]). Using the NASCET criteria, the percentual degree of luminal restriction was calculated. Results: In total, 20 angiographic 3D volumes (n3DA = 10; n3D-DSA = 10) were successfully reconstructed with equivalent IQ. Assessment of the vessel geometry in 3DA datasets did not differ significantly from 3D-DSA (VD1: r = 0.994, p = 0.0001; VD2:r = 0.994, p = 0.0001; VGI: r = 0.899, p = 0.0001). Qualitative analysis of IAS location (3DA/3D-DSA:nICA/C4 = 1, nICA/C7 = 1, nMCA/M1 = 4, nVA/V4 = 2, nBA = 2) and the visual IAS grading (3DA/3D-DSA:nlow-grade = 3, nmedium-grade = 5, nhigh-grade = 2) revealed identical results for 3DA and 3D-DSA, respectively. Quantitative IAS assessment showed a strong correlation regarding intra-/poststenotic diameters (rdintrastenotic = 0.995, pdintrastenotic = 0.0001; rdpoststenotic = 0.995, pdpoststenotic = 0.0001) and the percentual degree of luminal restriction (rNASCET 3DA = 0.981; pNASCET 3DA = 0.0001). Conclusions: The AI-based 3DA is a resilient algorithm for the visualization of IAS and shows comparable results to 3D-DSA. Hence, 3DA is a promising new method that allows a considerable patient-dose reduction, and its clinical implementation would be highly desirable.
CRIS-Team Scopus Importer:2023-03-10
Keywords: 3D angiography; artificial intelligence; deep learning; dose reduction; flat-detector computed tomography (FD-CT); innovative postprocessing; intracranial artery stenosis

A Comparison of Single- and Multiparametric MRI Models for Differentiation of Recurrent Glioblastoma from Treatment-Related Change - Eisenhut, Felix; Engelhorn, Tobias; Arinrad, Soheil; Brandner, Sebastian; Coras, Roland; Putz, Florian; Fietkau, Rainer; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2021)
To evaluate single- and multiparametric MRI models to differentiate recurrent glioblastoma (GBM) and treatment-related changes (TRC) in clinical routine imaging. Selective and unselective apparent diffusion coefficient (ADC) and minimum, mean, and maximum cerebral blood volume (CBV) measurements in the lesion were performed. Minimum, mean, and maximum ratios(CBV) (CBVlesion to CBVhealthy white matter) were computed. All data were tested for lesion discrimination. A multiparametric model was compiled via multiple logistic regression using data demonstrating significant difference between GBM and TRC and tested for its diagnostic strength in an independent patient cohort. A total of 34 patients (17 patients with recurrent GBM and 17 patients with TRC) were included. ADC measurements showed no significant difference between both entities. All CBV and ratios(CBV) measurements were significantly higher in patients with recurrent GBM than TRC. A minimum CBV of 8.5, mean CBV of 116.5, maximum CBV of 327 and ratio(CBV) (minimum) of 0.17, ratio(CBV) (mean) of 2.26 and ratio(CBV) (maximum) of 3.82 were computed as optimal cut-off values. By integrating these parameters in a multiparametric model and testing it in an independent patient cohort, 9 of 10 patients, i.e., 90%, were classified correctly. The multiparametric model further improves radiological discrimination of GBM from TRC in comparison to single-parameter approaches and enables reliable identification of recurrent tumors.
CRIS-Team WoS Importer:2022-01-07

Amyloid-beta levels and cognitive trajectories in non-demented pTau181-positive subjects without amyloidopathy - Oberstein, Timo; Schmidt, Manuel; Florvaag, Anna; Haas, Anna-Lena; Siegmann, Eva-Maria; Olm, Pauline; Utz, Janine; Spitzer, Philipp; Dörfler, Arnd; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel (Brain, 2022)
In a long-term observational study, Oberstein et al. find that the biomarker constellation of increased pTau181, A beta 40 and A beta 42 in CSF is not associated with dementia. Further investigation of this biomarker profile may provide insights into the circumstances under which A beta becomes pathological.
CRIS-Team WoS Importer:2022-09-30

Angioedema in Stroke Patients With Thrombolysis - Fröhlich, Katharina; Macha, Kosmas; Gerner, Stefan; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Hilz, Max-Josef; Schwab, Stefan; Seifert, Frank; Kallmünzer, Bernd; Winder, Klemens (Stroke, 2019)
Background and Purpose- Oral angioedema (OA) is a rare but life-threatening complication in patients with ischemic stroke receiving intravenous thrombolysis with r-tPA (recombinant tissue-type plasminogen activator). This study intended to determine associations between thrombolysis-related OA and ischemic stroke lesion sites using a voxel-wise lesion analysis. Methods- Prospective registry data were used to identify ischemic stroke patients with thrombolysis-related OA between 2002 and 2018. For the study registry, ethics approval was obtained by the Ethics Committee of the Friedrich-Alexander Universität (FAU) Erlangen-Nürnberg (clinical registry registration: 377_17Bc). Ischemic stroke patients with thrombolysis treatment but without OA admitted in the years 2011 and 2012 comprised the control group. Ischemic lesions were manually outlined on magnetic resonance imaging (1.5T or 3T) or computed tomographic scans and transformed into stereotaxic space. We determined the lesion overlap and compared the absence or presence of OA voxel-wise between patients with and without lesions in a given voxel using the Liebermeister test. Stroke severity was rated using the National Institutes of Health Stroke Scale score, and blood pressure, heart rate, blood glucose levels, and body temperature were determined on admission. Results- Fifteen ischemic stroke patients with thrombolysis-related OA were identified. The voxel-wise analysis yielded associations between OA and ischemic lesions in the insulo-opercular region with a right hemispheric dominance. Mean blood pressure was significantly lower in patients with OA than in controls. Age, National Institutes of Health Stroke Scale scores, infarct volumes, heart rate, and blood glucose levels did not differ between patients with and without OA. Conclusions- The voxel-wise analysis linked thrombolysis-related OA to right insulo-opercular lesions. The lower blood pressure in patients with thrombolysis-related OA may reflect bradykinin effects causing vasodilatation and increasing vascular permeability.
CRIS-Team Scopus Importer:2019-07-19
Keywords: angioedema; autonomic nervous system; brain ischemia; neuroimaging; stroke; tissue-type plasminogen activator

Artificial intelligence-based 3D angiography for visualization of complex cerebrovascular pathologies - Lang, Sabine; Hölter, Philip; Schmidt, Manuel; Strother, C.; Kaethner, C.; Kowarschik, M.; Dörfler, Arnd (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: By means of artificial intelligence, 3D angiography is a novel postprocessing method for 3D imaging of cerebral vessels. Because 3D angiography does not require a mask run like the current standard 3D-DSA, it potentially offers a considerable reduction of the patient radiation dose. Our aim was an assessment of the diagnostic value of 3D angiography for visualization of cerebrovascular pathologies. MATERIALS AND METHODS: 3D-DSA data sets of cerebral aneurysms (nCA ¼ 10), AVMs (nAVM ¼ 10), and dural arteriovenous fistulas (dAVFs) (ndAVF ¼ 10) were reconstructed using both conventional and prototype software. Corresponding reconstructions have been analyzed by 2 neuroradiologists in a consensus reading in terms of image quality, injection vessel diameters (vessel diameter [VD] 1/2), vessel geometry index (VGI ¼ VD1/VD2), and specific qualitative/quantitative parameters of AVMs (eg, location, nidus size, feeder, associated aneurysms, drainage, Spetzler-Martin score), dAVFs (eg, fistulous point, main feeder, diameter of the main feeder, drainage), and cerebral aneurysms (location, neck, size). RESULTS: In total, 60 volumes have been successfully reconstructed with equivalent image quality. The specific qualitative/quantitative assessment of 3D angiography revealed nearly complete accordance with 3D-DSA in AVMs (eg, mean nidus size3D angiography/3D-DSA¼ 19.9 [SD, 10.9]/20.2 [SD, 11.2] mm; r ¼ 0.9, P ¼.001), dAVFs (eg, mean diameter of the main feeder3D angiography/3D-DSA¼ 2.04 [SD, 0.65]/2.05 [SD, 0.63] mm; r ¼ 0.9, P ¼.001), and cerebral aneurysms (eg, mean size3D angiography/3D-DSA¼ 5.17 [SD, 3.4]/5.12 [SD, 3.3] mm; r ¼ 0.9, P ¼.001). Assessment of the geometry of the injection vessel in 3D angiography data sets did not differ significantly from that of 3D-DSA (vessel geometry indexAVM: r ¼ 0.84, P ¼.003; vessel geometry indexdAVF: r ¼ 0.82, P ¼.003; vessel geometry indexCA: r ¼ 0.84, P,.001). CONCLUSIONS: In this study, the artificial intelligence-based 3D angiography was a reliable method for visualization of complex cerebrovascular pathologies and showed results comparable with those of 3D-DSA. Thus, 3D angiography is a promising postprocessing method that provides a significant reduction of the patient radiation dose.
CRIS-Team Scopus Importer:2021-11-05

Ascending axonal degeneration of the corticospinal tract in pure hereditary spastic paraplegia: A cross-sectional DTI study - List, Julia; Kohl, Zacharias; Winkler, Jürgen; Marxreiter, Franz; Dörfler, Arnd; Schmidt, Manuel (Brain Sciences, 2019)
Objective: To identify structural white matter alterations in patients with pure hereditary spastic paraplegia (HSP) using high angular resolution diffusion tensor imaging (DTI). Methods: We examined 37 individuals with high resolution DTI, 20 patients with pure forms of hereditary spastic paraplegia and 17 age and gender matched healthy controls. DTI was performed using a 3 T clinical scanner with whole brain tract-based spatial statistical (TBSS) analysis of the obtained fractional anisotropy (FA) data as well as a region-of-interest (ROI)-based analysis of affected tracts including the cervical spinal cord. We further conducted correlation analyses between DTI data and clinical characteristics. Results: TBSS analysis in HSP patients showed significantly decreased fractional anisotropy of the corpus callosum and the corticospinal tract compared to healthy controls. ROI-based analysis confirmed significantly lower FA in HSP compared to controls in the internal capsule (0.77 vs. 0.80, p = 0.048), the corpus callosum (0.84 vs. 0.87, p = 0.048) and the cervical spinal cord (0.72 vs. 0.79, p = 0.003). FA values of the cervical spinal cord significantly correlated with disease duration. Conclusion: DTI metrics of the corticospinal tract from the internal capsule to the cervical spine suggest microstructural damage and axonal degeneration of motor neurons. The CST at the level of the cervical spinal cord is thereby more severely affected than the intracranial part of the CST, suggesting an ascending axonal degeneration of the CST. Since there is a significant correlation with disease duration, FA may serve as a future progression marker for assessment of the disease course in HSP.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Corticospinal tract; Diffusion tensor imaging; Fractional anisotropy; Hereditary spastic paraplegia; Tract-based spatial statistics (TBSS)

Brain tissues have single-voxel signatures in multi-spectral MRI - German, Alexander; Mennecke, Angelika; Martin, Jan; Hanspach, Jannis; Liebert, Andrzej; Herrler, Jürgen; Kuder, Tristan Anselm; Schmidt, Manuel; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Winkler, Jürgen; et al. (NeuroImage, 2021)
Since the seminal works by Brodmann and contemporaries, it is well-known that different brain regions exhibit unique cytoarchitectonic and myeloarchitectonic features. Transferring the approach of classifying brain tissues – and other tissues – based on their intrinsic features to the realm of magnetic resonance (MR) is a longstanding endeavor. In the 1990s, atlas-based segmentation replaced earlier multi-spectral classification approaches because of the large overlap between the class distributions. Here, we explored the feasibility of performing global brain classification based on intrinsic MR features, and used several technological advances: ultra-high field MRI, q-space trajectory diffusion imaging revealing voxel-intrinsic diffusion properties, chemical exchange saturation transfer and semi-solid magnetization transfer imaging as a marker of myelination and neurochemistry, and current neural network architectures to analyze the data. In particular, we used the raw image data as well to increase the number of input features. We found that a global brain classification of roughly 97 brain regions was feasible with gross classification accuracy of 60%; and that mapping from voxel-intrinsic MR data to the brain region to which the data belongs is possible. This indicates the presence of unique MR signals of different brain regions, similar to their cytoarchitectonic and myeloarchitectonic fingerprints.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Brain; Data Analysis; High-Field Imaging; Machine Learning; MRI; Segmentation

Brain volume reduction after whole-brain radiotherapy: quantification and prognostic relevance - Hoffmann, Christian; Distel, Luitpold; Knippen, Stefan; Gryc, Thomas; Schmidt, Manuel; Fietkau, Rainer; Putz, Florian (Neuro-Oncology, 2018)
Background: Recent studies have questioned the value of adding whole-brain radiotherapy (WBRT) to stereotactic radiosurgery (SRS) for brain metastasis treatment. Neurotoxicity, including radiation-induced brain volume reduction, could be one reason why not all patients benefit from the addition of WBRT. In this study, we quantified brain volume reduction after WBRT and assessed its prognostic significance. Methods: Brain volumes of 91 patients with cerebral metastases were measured during a 150-day period after commencing WBRT and were compared with their pretreatment volumes. The average daily relative change in brain volume of each patient, referred to as the "brain volume reduction rate," was calculated. Univariate and multivariate Cox regression analyses were performed to assess the prognostic significance of the brain volume reduction rate, as well as of 3 treatment-related and 9 pretreatment factors. A one-way analysis of variance was used to compare the brain volume reduction rate across recursive partitioning analysis (RPA) classes. Results: On multivariate Cox regression analysis, the brain volume reduction rate was a significant predictor of overall survival after WBRT (P < 0.001), as well as the number of brain metastases (P = 0.002) and age (P = 0.008). Patients with a relatively favorable prognosis (RPA classes 1 and 2) experienced significantly less brain volume decrease after WBRT than patients with a poor prognosis (RPA class 3) (P = 0.001). There was no significant correlation between delivered radiation dose and brain volume reduction rate (P = 0.147). Conclusion: In this retrospective study, a smaller decrease in brain volume after WBRT was an independent predictor of longer overall survival.
EVALuna2:36468

Can Perfusion-Based Brain Tissue Oxygenation MRI Support the Understanding of Cerebral Abscesses In Vivo? - Knott, Michael; Hölter, Philip; Soder, Liam; Schlaffer, Sven-Martin; Hoffmanns, Sophia; Lang, Roland; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2023)
Purpose: The clinical condition of a brain abscess is a potentially life-threatening disease. The combination of MRI-based imaging, surgical therapy and microbiological analysis is critical for the treatment and convalescence of the individual patient. The aim of this study was to evaluate brain tissue oxygenation measured with dynamic susceptibility contrast perfusion weighted imaging (DSC-PWI) in patients with brain abscess and its potential benefit for a better understanding of the environment in and around brain abscesses. Methods: Using a local database, 34 patients (with 45 abscesses) with brain abscesses treated between January 2013 and March 2021 were retrospectively included in this study. DSC-PWI imaging and microbiological work-up were key inclusion criteria. These data were analysed regarding a correlation between DSC-PWI and microbiological result by quantifying brain tissue oxygenation in the abscess itself, the abscess capsula and the surrounding oedema and by using six different parameters (CBF, CBV, CMRO2, COV, CTH and OEF). Results: Relative cerebral blood flow (0.335 [0.18–0.613] vs. 0.81 [0.49–1.08], p = 0.015), relative cerebral blood volume (0.44 [0.203–0.72] vs. 0.87 [0.67–1.2], p = 0.018) and regional cerebral metabolic rate for oxygen (0.37 [0.208–0.695] vs. 0.82 [0.55–1.19], p = 0.022) were significantly lower in the oedema around abscesses without microbiological evidence of a specific bacteria in comparison with microbiological positive lesions. Conclusions: The results of this study indicate a relationship between brain tissue oxygenation status in DSC-PWI and microbiological/inflammatory status. These results may help to better understand the in vivo environment of brain abscesses and support future therapeutic decisions.
CRIS-Team Scopus Importer:2023-11-24
Keywords: brain abscess; brain tissue oxygenation; DSC-PWI

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Change your Angle of View Sinusoidal C-Arm Movement in Cranial Flat-panel CT to Improve Image Quality - Lücking, Hannes; Hölter, Philip; Lang, Stefan; Schmidt, Manuel; Eisenhut, Felix; Dörfler, Arnd (Clinical Neuroradiology, 2022)
Background Artifacts from surrounding bony structures, especially from the petrous bones, regularly impair soft tissue computed tomography (CT) imaging of the middle and posterior fossa. This affects flat-panel CT in particular. Sinusoidal movement of the C-arm during acquisition (i.e. craniocaudal tilting along with semicircular rotation) is supposed to reduce artifacts, thus enhancing soft tissue imaging quality. Methods In the work-up of ischemic stroke or subarachnoid hemorrhage 40 patients underwent multi-slice CT (MS-CT) and either plain circular (cFP-CT; n = 20) or sinusoidal (sFP-CT; n = 20) flat-panel CT within a short interval. Two independent readers analyzed MS-CT and FP-CT datasets for recognizability of eight different brain structures and three typical types of artifacts according to a predetermined score. Results Interrater reliability was moderate for cFP-CT (kappa = 0.575) and good to very good for ratings of MS-CT and sFP-CT (kappa = 0.651 to kappa = 1). MS-CT was rated to be significantly better than cFP-CT and sFP-CT (p < 0.0001) in the overall score. Yet, sFP-CT was rated to be significantly superior to cFP-CT (overall p < 0.0001) regarding most anatomical regions and petrous bone artifacts. Conclusion Compared to a standard circular protocol, sinusoidal C-arm movement in cranial FP-CT can significantly reduce artifacts in the posterior fossa and, moreover, can improve visualization of most supratentorial and infratentorial anatomical structures.
CRIS-Team WoS Importer:2022-05-20

Classification of primary cerebral lymphoma and glioblastoma featuring dynamic susceptibility contrast and apparent diffusion coefficient - Eisenhut, Felix; Schmidt, Manuel; Putz, Florian; Lettmaier, Sebastian; Fröhlich, Kilian; Arinrad, Soheil; Coras, Roland; Lücking, Hannes; Lang, Stefan; Fietkau, Rainer; Dörfler, Arnd (Brain Sciences, 2020)
This study aimed to differentiate primary central nervous system lymphoma (PCNSL) and glioblastoma (GBM) via multimodal MRI featuring radiomic analysis. MRI data sets of patients with histological proven PCNSL and GBM were analyzed retrospectively. Diffusion-weighted imaging (DWI) and dynamic susceptibility contrast (DSC) perfusion imaging were evaluated to differentiate contrast enhancing intracerebral lesions. Selective (contrast enhanced tumor area with the highest mean cerebral blood volume (CBV) value) and unselective (contouring whole contrast enhanced lesion) Apparent diffusion coefficient (ADC) measurement was performed. By multivariate logistic regression, a multiparametric model was compiled and tested for its diagnostic strength. A total of 74 patients were included in our study. Selective and unselective mean and maximum ADC values, mean and maximum CBV and ratioCBV as quotient of tumor CBV and CBV in contralateral healthy white matter were significantly larger in patients with GBM than PCNSL; minimum CBV was significantly lower in GBM than in PCNSL. The highest AUC for discrimination of PCNSL and GBM was obtained for selective mean and maximum ADC, mean and maximum CBV and ratioCBV. By integrating these five in a multiparametric model 100% of the patients were classified correctly. The combination of perfusion imaging (CBV) and tumor hot-spot selective ADC measurement yields reliable radiological discrimination of PCNSL from GBM with highest accuracy and is readily available in clinical routine.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ADC; DSC; Glioblastoma; MRI; Multimodal; Primary central nervous system lymphoma

Clinical Evaluation of an Innovative Metal-Artifact-Reduction Algorithm in FD-CT Angiography in Cerebral Aneurysms Treated by Endovascular Coiling or Surgical Clipping - Eisenhut, Felix; Schmidt, Manuel; Kalik, Alexander; Struffert, Tobias; Feulner, Julian; Schlaffer, Sven-Martin; Manhart, Michael; Dörfler, Arnd; Lang, Stefan (Diagnostics, 2022)
Treated cerebral aneurysms (IA) require follow-up imaging to ensure occlusion. Metal artifacts complicate radiologic assessment. Our aim was to evaluate an innovative metal-artifact-reduction (iMAR) algorithm for flat-detector computed tomography angiography (FD-CTA) regarding image quality (IQ) and detection of aneurysm residua/reperfusion in comparison to 2D digital subtraction angiography (DSA). Patients with IAs treated by endovascular coiling or clipping underwent both FD-CTA and DSA. FD-CTA datasets were postprocessed with/without iMAR algorithm (MAR+/MAR−). Evaluation of all FD-CTA and DSA datasets regarding qualitative (IQ, MAR) and quantitative (coil package diameter/CPD) parameters was performed. Aneurysm occlusion was assessed for each dataset and compared to DSA findings. In total, 40 IAs were analyzed (ncoiling = 24; nclipping = 16). All iMAR+ datasets demonstrated significantly better IQ (pIQ coiling < 0.0001; pIQ clipping < 0.0001). iMAR significantly reduced the metal-artifact burden but did not affect the CPD. iMAR significantly improved the detection of aneurysm residua/reperfusion with excellent agreement with DSA (naneurysm detection MAR+/MAR−/DSA = 22/1/26). The iMAR algorithm significantly improves IQ by effective reduction of metal artifacts in FD-CTA datasets. The proposed algorithm enables reliable detection of aneurysm residua/reperfusion with good agreement to DSA. Thus, iMAR can help to reduce the need for invasive follow-up in treated IAs.
CRIS-Team Scopus Importer:2022-05-27
Keywords: cerebral aneurysm; endovascular coiling; flat-detector computed tomography angiography; metal-artifact-reduction algorithm; surgical clipping

Comprehensive 7 T CEST: A clinical MRI protocol covering multiple exchange rate regimes - Fabian, Moritz; Rajput, Junaid Rasool; Schüre, Jan-Rüdiger; Weinmüller, Simon; Mennecke, Angelika; Möhle, Tim Alexius; Rampp, Stefan; Schmidt, Manuel; Dörfler, Arnd; Zaiß, Moritz (NMR in Biomedicine, 2024)
SECTIONSPDFPDFTOOLS SHARE Abstract Chemical exchange saturation transfer (CEST) is a magnetic resonance (MR) imaging method providing molecular image contrasts based on indirect detection of low concentrated solutes. Previous CEST studies focused predominantly on the imaging of single CEST exchange regimes (e.g., slow, intermediate or fast exchanging groups). In this work, we aim to establish a so-called comprehensive CEST protocol for 7 T, covering the different exchange regimes by three saturation B1 amplitude regimes: low, intermediate and high. We used the results of previous publications and our own simulations in pulseq-CEST to produce a 7 T CEST protocol that has sensitivity to these three B1 regimes. With postprocessing optimization (simultaneous mapping of water shift and B1, B0-fitting, multiple interleaved mode saturation B1 correction, neural network employment (deepCEST) and analytical input feature reduction), we are able to shorten our initially 40 min protocol to 15 min and generate six CEST contrast maps simultaneously. With this protocol, we measured four healthy subjects and one patient with a brain tumor. We established a comprehensive CEST protocol for clinical 7 T MRI, covering three different B1 amplitude regimes. We were able to reduce the acquisition time significantly by more than 50%, while still maintaining decent image quality and contrast in healthy subjects and one patient with a tumor. Our protocol paves the way to perform comprehensive CEST studies in clinical scan times for hypothesis generation regarding molecular properties of certain pathologies, for example, ischemic stroke or high-grade brain tumour

Comprehensive Multimodal Deep Learning Survival Prediction Enabled by a Transformer Architecture: A Multicenter Study in Glioblastoma - Gomaa, Ahmed; Huang, Yixing; Hagag, Amr; Schmitter, Charlotte; Höfler, Daniel; Weissmann, Thomas; Breininger, Katharina; Schmidt, Manuel; Stritzelberger, Jenny; Delev, Daniel; Coras, Roland; Dörfler, Arnd; et al. (Neuro-Oncology Advances, 2024)
Keywords: Survival prediction; deep learning; glioblastoma; MR; prognosis; multimodal data

DeepCEST 7 T: Fast and homogeneous mapping of 7 T CEST MRI parameters and their uncertainty quantification - Hunger, Leonie; Rajput, Junaid Rasool; Klein, Kiril; Mennecke, Angelika; Fabian, Moritz; Schmidt, Manuel; Glang, Felix; Herz, Kai; Liebig, Patrick; Nagel, Armin Michael; Scheffler, Klaus; Dörfler, Arnd; et al. (Magnetic Resonance in Medicine, 2022)
Purpose In this work, we investigated the ability of neural networks to rapidly and robustly predict Lorentzian parameters of multi-pool CEST MRI spectra at 7 T with corresponding uncertainty maps to make them quickly and easily available for routine clinical use. Methods We developed a deepCEST 7 T approach that generates CEST contrasts from just 1 scan with robustness against B-1 inhomogeneities. The input data for a neural feed-forward network consisted of 7 T in vivo uncorrected Z-spectra of a single B-1 level, and a B-1 map. The 7 T raw data were acquired using a 3D snapshot gradient echo multiple interleaved mode saturation CEST sequence. These inputs were mapped voxel-wise to target data consisting of Lorentzian amplitudes generated conventionally by 5-pool Lorentzian fitting of normalized, denoised, B-0- and B-1-corrected Z-spectra. The deepCEST network was trained with Gaussian negative log-likelihood loss, providing an uncertainty quantification in addition to the Lorentzian amplitudes. Results The deepCEST 7 T network provides fast and accurate prediction of all Lorentzian parameters also when only a single B-1 level is used. The prediction was highly accurate with respect to the Lorentzian fit amplitudes, and both healthy tissues and hyperintensities in tumor areas are predicted with a low uncertainty. In corrupted cases, high uncertainty indicated wrong predictions reliably. Conclusion The proposed deepCEST 7 T approach reduces scan time by 50% to now 6:42 min, but still delivers both B-0- and B-1-corrected homogeneous CEST contrasts along with an uncertainty map, which can increase diagnostic confidence. Multiple accurate 7 T CEST contrasts are delivered within seconds.
CRIS-Team WoS Importer:2022-12-02

Deep learning for brain metastasis detection and segmentation in longitudinal MRI data - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Medical Physics, 2022)
Keywords: Deep learning; brain metastasis; MRI; loss function; sensitivity specificity

Direct imaging of white matter ultrashort T2∗ components at 7 Tesla - Müller, Max; Egger, Nico; Sommer, Stefan; Wilferth, Tobias; Meixner, Christian; Laun, Frederik Bernd; Mennecke, Angelika; Schmidt, Manuel; Huhn, Konstantin; Rothhammer, Veit; Uder, Michael; Dörfler, Arnd; et al. (Magnetic Resonance Imaging, 2022)
Purpose: To demonstrate direct imaging of the white matter ultrashort T2∗ components at 7 Tesla using inversion recovery (IR)-enhanced ultrashort echo time (UTE) MRI. To investigate its characteristics, potentials and limitations, and to establish a clinical protocol. Material and methods: The IR UTE technique suppresses long T2∗ signals within white matter by using adiabatic inversion in combination with dual-echo difference imaging. Artifacts arising at 7 T from long T2∗ scalp fat components were reduced by frequency shifting the IR pulse such that those frequencies were inverted likewise. For 8 healthy volunteers, the T2∗ relaxation times of white matter were then quantified. In 20 healthy volunteers, the UTE difference and fraction contrast were evaluated. Finally, in 6 patients with multiple sclerosis (MS), the performance of the technique was assessed. Results: A frequency shift of −1.2 ppm of the IR pulse (i.e. towards the fat frequency) provided a good suppression of artifacts. With this, an ultrashort compartment of (68 ± 6) % with a T2∗ time of (147 ± 58) μs was quantified with a chemical shift of (−3.6 ± 0.5) ppm from water. Within healthy volunteers' white matter, a stable ultrashort T2∗ fraction contrast was calculated. For the MS patients, a significant fraction reduction in the identified lesions as well as in the normal-appearing white matter was observed. Conclusions: The quantification results indicate that the observed ultrashort components arise primarily from myelin tissue. Direct IR UTE imaging of the white matter ultrashort T2∗ components is thus feasible at 7 T with high quantitative inter-subject repeatability and good detection of signal loss in MS.
Created from Fastlane, Scopus look-up
Keywords: 7 Tesla; Multiple sclerosis; Myelin; Relaxometry; Ultrashort echo time (UTE); White matter

Distinguishing Progression and Radionecrosis in large progressive Brain Metastases after Stereotaxy by integrating Radiomics, Dose Radiomics and clinical Risk Factors - Sommer, Phillip; Huang, Yixing; Srinivasan, Aishwarya Lakshmi; Fischer, Stefan; Dörfler, Arnd; Schmidt, Manuel; Frey, Benjamin; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

DSC Brain Perfusion Using Advanced Deconvolution Models in the Diagnostic Work-Up of Dementia and Mild Cognitive Impairment: A Semiquantitative Comparison with HMPAO-SPECT-Brain Perfusion - Schmidt, Manuel; Engelhorn, Tobias; Lang, Stefan; Lücking, Hannes; Hölter, Philip; Fröhlich, Kilian; Ritt, Philipp; Maler, Juan Manuel; Kuwert, Torsten; Kornhuber, Johannes; Dörfler, Arnd (Journal of Clinical Medicine, 2020)
Background: SPECT (single-photon emission-computed tomography) is used for the detection of hypoperfusion in cognitive impairment and dementia but is not widely available and related to radiation dose exposure. We compared the performance of DSC (dynamic susceptibility contrast) perfusion using semi- and fully adaptive deconvolution models to HMPAO-SPECT (99mTc-hexamethylpropyleneamine oxime-SPECT). Material and Methods: Twenty-seven patients with dementia of different subtypes including frontotemporal dementia (FTD) and mild cognitive impairment (MCI) received a multimodal diagnostic work-up including DSC perfusion at a clinical 3T high-field scanner and HMPAO-SPECT. Nineteen healthy control individuals received DSC perfusion. For calculation of the hemodynamic parameter maps, oscillation-index standard truncated singular value decomposition (oSVD, semi-adaptive) as well as Bayesian parameter estimation (BAY, fully adaptive) were performed. Results: Patients showed decreased cortical perfusion in the left frontal lobe compared to controls (relative cerebral blood volume corrected, rBVc: 0.37 vs. 0.27,p= 0.048, adjusted for age and sex). Performance of rBVc (corrected for T1 effects) was highest compared to SPECT for detection of frontal hypoperfusion (sensitivity 83%, specificity 80% for oSVD and BAY, area under curve (AUC) = 0.833 respectively,p< 0.05) in FTD and MCI. For nonleakage-corrected rBV and for rBF (relative cerebral blood flow), sensitivity of frontal hypoperfusion was above 80% for oSVD and for BAY (rBV: sensitivity 83%, specificity 75%, AUC = 0.908 for oSVD and 0.917 for BAY,p< 0.05 respectively; rBF: sensitivity 83%, specificity 65%, AUC = 0.825,p< 0.05 for oSVD). Conclusion: Advanced deconvolution DSC can reliably detect pathological perfusion alterations in FTD and MCI. Hence, this widely accessible technique has the potential to improve the diagnosis of dementia and MCI as part of an interdisciplinary multimodal imaging work-up. Advances in knowledge: Advanced DSC perfusion has a high potential in the work-up of suspected dementia and correlates with SPECT brain perfusion results in dementia and MCI.
CRIS-Team WoS Importer:2020-07-31

DTI analysis in patients with primary open-angle glaucoma: impact of registration on Voxel-Wise statistics - Schmidt, Manuel; Mennecke, Angelika; Michelson, Georg; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2014)
Tract-based spatial statistics (TBSS) has been used to assess the integrity of the visual pathway in glaucoma patients. TBSS uses the subjects' FA data to create a mean FA skeleton of white matter tracts before running voxel-wise cross-subject statistics. We compared four different approaches of registration of FA maps to create the skeleton and evaluated alignment and subsequently the impact of the chosen registration on voxel-wise statistics.Our study comprised 69 subjects, i.e. 46 patients with primary open angle glaucoma (POAG) and a healthy, age-matched control group of 23 subjects. Mean FA skeletons were created using the following registration approaches: registration to a standard template (T), registration to the group mean (GM), registration to a group-wise atlas (GW) and registration to the most typical subject (N). Subsequently, maps of standard deviation of the 4D images were created to assess the alignment. Voxel-wise statistics for each registration approach were performed.We found distinct differences in voxel-wise statistics depending on the chosen registration approach. Best alignment results were achieved by registration to a study specific template, i.e. to the group mean (GM) or to a group-wise atlas (GW). Overall alignment did not differ between these two approaches. However, voxel-wise statistics showed clusters of significantly decreased FA values in the T and GM approach, which were not significant after GW registration. These voxels of significantly decreased FA values after T and GM registration did not represent white matter tracts and correlated with higher standard deviation in FA maps across subjects, thus implying registration errors, especially in the optic radiation.Registration to a study-specific template, i.e. to the group mean or a group-wise atlas seems to be the method of choice in TBSS-analysis of glaucoma patients as it shows better alignment of the optic radiation and helps to rule out registration errors due to misalignment.
EVALuna2:21168

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

Effects of Hippocampal Sparing Radiotherapy on Brain Microstructure—A Diffusion Tensor Imaging Analysis - Dinkel, Johannes; Lahmer, Godehard; Mennecke, Angelika; Hock, Stefan; Richter-Schmidinger, Tanja; Fietkau, Rainer; Distel, Luitpold; Putz, Florian; Dörfler, Arnd; Schmidt, Manuel (Brain Sciences, 2022)
Hippocampal-sparing radiotherapy (HSR) is a promising approach to alleviate cognitive side effects following cranial radiotherapy. Microstructural brain changes after irradiation have been demonstrated using Diffusion Tensor Imaging (DTI). However, evidence is conflicting for certain parameters and anatomic structures. This study examines the effects of radiation on white matter and hippocampal microstructure using DTI and evaluates whether these may be mitigated using HSR. A total of 35 tumor patients undergoing a prospective randomized controlled trial receiving either conventional or HSR underwent DTI before as well as 6, 12, 18, 24, and 30 (±3) months after radiotherapy. Fractional Anisotropy (FA), Mean Diffusivity (MD), Axial Diffusivity (AD), and Radial Diffusivity (RD) were measured in the hippocampus (CA), temporal, and frontal lobe white matter (TL, FL), and corpus callosum (CC). Longitudinal analysis was performed using linear mixed models. Analysis of the entire patient collective demonstrated an overall FACC decrease and RDCC increase compared to baseline in all follow-ups; ADCC decreased after 6 months, and MDCC increased after 12 months (p ≤ 0.001, 0.001, 0.007, 0.018). ADTL decreased after 24 and 30 months (p ≤ 0.004, 0.009). Hippocampal FA increased after 6 and 12 months, driven by a distinct increase in ADCA and MDCA, with RDCA not increasing until 30 months after radiotherapy (p ≤ 0.011, 0.039, 0.005, 0.040, 0.019). Mean radiation dose correlated positively with hippocampal FA (p < 0.001). These findings may indicate complex pathophysiological changes in cerebral microstructures after radiation, insufficiently explained by conventional DTI models. Hippocampal microstructure differed between patients undergoing HSR and conventional cranial radiotherapy after 6 months with a higher ADCA in the HSR subgroup (p ≤ 0.034).
CRIS-Team Scopus Importer:2022-07-22
Keywords: cognitive impairment; cranial radiotherapy; diffusion tensor imaging; fractional anisotropy; hippocampal sparing radiotherapy; hippocampus

Endovascular treatment in patients with large vessel occlusion: reduced mortality despite minimal penumbra - Schmidt, Manuel; Breuer, Lorenz; Kallmünzer, Bernd; Schwab, Stefan; Dörfler, Arnd; Engelhorn, Tobias; Hölter, Philip (Neuroradiology, 2019)
Purpose: In patients with acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), endovascular treatment (EVT) is highly effective for emergency revascularization. However, data on functional outcome are lacking for patients, which show no or minimal mismatch between ischemic core and penumbra. Methods: Forty-five patients with AIS due to LVO of the anterior circulation were retrospectively analyzed within 6 h since onset when administered to our department. In all patients, there was no relevant penumbra according to CT perfusion (CTP). Functional outcome, defined by the modified Rankin Scale (mRS) at 30 and 90 days, was analyzed according to LVO treatment (EVT versus non-EVT). Confounding was addressed by multivariable regression analyses. Results: mRS values at 30 days (p = 0.002) and 90 days (p = 0.005) after AIS occurrence were significantly lower in patients who had received EVT. There was no significant difference regarding good functional outcome, as measured by mRS of 0–2 at 30 (p = 0.432) and 90 days, respectively (p = 0.186). Mortality was significantly reduced in patients undergoing EVT at 30-day (p < 0.001) and at 90-day follow-up (p = 0.003), respectively. Multivariable regression analyses revealed that EVT was associated with reduced mortality at 30 (OR 0.091; CI (0.013–0.612); p = 0.014) and 90 days (OR 0.134; CI (0.021–0.857); p = 0.034) after AIS. Conclusions: Despite a small and highly selected patient collective, our study indicates that AIS patients with minimal penumbra in CTP might benefit from EVT in terms of reduced mortality at 30 and 90 days after AIS. However, in this group of patients, we could not prove favorable functional outcome at 30 and 90 days, despite receiving EVT.
CRIS-Team Scopus Importer:2019-09-17
Keywords: CTP; Endovascular treatment; Mortality; Penumbra; Stroke

Evaluation of an Artificial Intelligence-Based 3D-Angiography for Visualization of Cerebral Vasculature - Lang, Stefan; Schmidt, Manuel; Eisenhut, Felix; Kaethner, Christian; Kowarschik, Markus; Lücking, Hannes; Dörfler, Arnd; Hölter, Philip (Clinical Neuroradiology, 2019)
Purpose: The three-dimensional digital subtraction angiography (3D DSA) technique is the current standard and is based on both mask and fill runs to enable the subtraction technique. Artificial intelligence (AI)-based 3D angiography (3DA) was developed to reduce radiation dosage because only one contrast-enhanced run of the C‑arm system is required for reconstruction of DSA-like 3D volumes. The aim was the evaluation of this algorithm regarding its diagnostic information. Methods: 3D DSA datasets without pathologic findings were reconstructed both with subtraction technique and with the AI-based algorithm. Corresponding reconstructions were evaluated by 2 neuroradiologists with respect to image quality (IQ), visualization of major segments of the circle of Willis (ICA = C4-C7; OphA; ACA = A1-A2, MCA = M1-M2; VA = V4; BA; AICA; SUCA; PCA = P1-P2), identifiability of perforators (lenticulostriate/thalamoperforating arteries) and vessel diameters (ICA = C4; MCA = M1; BA; PCA = P1). Results: In total 15 datasets were successfully reconstructed as 3D DSA and 3DA with diagnostic image quality. All major segments of the circle of Willis and perforators were comparably visualized with 3DA. Quantitative analysis of vessel diameters in 3D DSA and 3DA datasets was equivalent and did not show relevant differences (rICA = 0.901, p = 0.001; rM1 = 0.951, p = 0.001; rBA = 0.906, p = 0.001; rP1 = 0.991, p = 0.001). Conclusions: The use of 3DA demonstrated reliable visualization of cerebral vasculature with respect to quantitative and qualitative parameters. Therefore, 3DA is a promising method that might help to reduce patient radiation.
CRIS-Team Scopus Importer:2019-11-01
Keywords: 3D angiography; Artificial intelligence; Deep learning; Dose reduction; Flat-detector computed tomography

Evidence for improved survival with bevacizumab treatment in recurrent high-grade gliomas: a retrospective study with ("pseudo-randomized") treatment allocation by the health insurance provider - Hofmann, Susanne; Schmidt, Manuel; Weissmann, Thomas; Eyüpoglu, Ilker Yasin; Strnad, Annedore; Semrau, Sabine; Fietkau, Rainer; Putz, Florian; Lettmaier, Sebastian (Journal of Neuro-Oncology, 2020)
Introduction Despite a large number of trials, the role of bevacizumab (BEV) in the treatment of recurrent high-grade gliomas is still controversial. Evidence regarding an effect on overall survival in this context is ultimately inconclusive. At the Department of Radiation Oncology at Erlangen, Germany we treated a large cohort of patients with recurrent gliomas where bevacizumab use was determined exclusively by the health care provider's approval of reimbursement. Methods 61 patients (between 06/2008 and 01/2014) with recurrent high-grade gliomas had reimbursement requests for BEV sent to their health insurance. 37 patients out of 61 (60.7%) had their requests approved and therefore received bevacizumab (BEV-arm) as part of their treatment. The remaining 24 (39.3%) patients received standard therapy without bevacizumab (non-BEV-arm). Survival endpoints were defined with reference to the first BEV request to the health insurance provider. Results Median overall survival (OS) for the whole cohort was 7.0 months. OS was significantly better for BEV vs. Non-BEV patients (median, 10.3 vs. 4.2 months, logrank p = 0.023). There was an increased BEV benefit in cases of higher-order recurrences (first order recurrence BEV vs. Non-BEV, 12.5 vs. 10.2 months, p = 0.578) (second or higher order of recurrence, 9.9 vs. 2.6 months, p = 0.010). On multivariate analysis for overall survival the prognostic impact of bevacizumab (HR = 0.43, p = 0.034) remained significant. Conclusion Our results suggest an influence of BEV on overall survival in a heavily pretreated patient population suffering from high-grade gliomas with BEV benefit being greatest in case of second or later recurrence.
CRIS-Team WoS Importer:2020-05-29

Expertenempfehlung zur Magnetresonanztomographie bei Muskelerkrankungen - Zeng, Rachel; Schlaeger, Sarah; Türk, Matthias; Baum, Thomas; Deschauer, Marcus; Janka, Rolf Matthias; Karampinos, Dimitrios; Kassubek, Jan; Keller-Yamamura, Sarah; Kornblum, Cornelia; Lehmann, Helmar; Lichtenstein, Thorsten; et al. (Der Nervenarzt, 2024)
Background: Magnetic resonance (MRI) imaging of the skeletal muscles (muscle MRI for short) is increasingly being used in clinical routine for diagnosis and longitudinal assessment of muscle disorders. However, cross-centre standards for measurement protocol and radiological assessment are still lacking. Objectives: The aim of this expert recommendation is to present standards for the application and interpretation of muscle MRI in hereditary and inflammatory muscle disorders. Methods: This work was developed in collaboration between neurologists, neuroradiologists, radiologists, neuropaediatricians, neuroscientists and MR physicists from different university hospitals in Germany. The recommendations are based on expert knowledge and a focused literature search. Results: The indications for muscle MRI are explained, including the detection and monitoring of structural tissue changes and oedema in the muscle, as well as the identification of a suitable biopsy site. Recommendations for the examination procedure and selection of appropriate MRI sequences are given. Finally, steps for a structured radiological assessment are presented. Conclusions: The present work provides concrete recommendations for the indication, implementation and interpretation of muscle MRI in muscle disorders. Furthermore, it provides a possible basis for the standardisation of the measurement protocols at all clinical centres in Germany.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Diagnostics; Muscle MRI; Myopathy; Myositis; Semi-quantitative assessment scales

Expertenempfehlung zur Magnetresonanztomographie bei Muskelerkrankungen - Zeng, Rachel; Schlaeger, Sarah; Türk, Matthias; Baum, Thomas; Deschauer, Marcus; Janka, Rolf Matthias; Karampinos, Dimitrios; Kassubek, Jan; Keller-Yamamura, Sarah; Kornblum, Cornelia; Lehmann, Helmar; Lichtenstein, Thorsten; et al. (Die Radiologie, 2024)
BACKGROUND: Magnetic resonance (MRI) imaging of the skeletal muscles (muscle MRI for short) is increasingly being used in clinical routine for diagnosis and longitudinal assessment of muscle disorders. However, cross-centre standards for measurement protocol and radiological assessment are still lacking. OBJECTIVES: The aim of this expert recommendation is to present standards for the application and interpretation of muscle MRI in hereditary and inflammatory muscle disorders. METHODS: This work was developed in collaboration between neurologists, neuroradiologists, radiologists, neuropaediatricians, neuroscientists and MR physicists from different university hospitals in Germany. The recommendations are based on expert knowledge and a focused literature search. RESULTS: The indications for muscle MRI are explained, including the detection and monitoring of structural tissue changes and oedema in the muscle, as well as the identification of a suitable biopsy site. Recommendations for the examination procedure and selection of appropriate MRI sequences are given. Finally, steps for a structured radiological assessment are presented. CONCLUSIONS: The present work provides concrete recommendations for the indication, implementation and interpretation of muscle MRI in muscle disorders. Furthermore, it provides a possible basis for the standardisation of the measurement protocols at all clinical centres in Germany.
EVALuna2:566089

Fast online-customized (FOCUS) parallel transmission pulses: A combination of universal pulses and individual optimization - Herrler, Jürgen; Liebig, Patrick; Gumbrecht, Rene; Ritter, Dieter; Schmitter, Sebastian; Maier, Andreas; Schmidt, Manuel; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2021)
Purpose: To mitigate spatial flip angle (FA) variations under strict specific absorption rate (SAR) constraints for ultra-high field MRI using a combination of universal parallel transmit (pTx) pulses and fast subject-specific optimization. Methods: Data sets consisting of B0, (Formula presented.) maps, and virtual observation point (VOP) data were acquired from 72 subjects (study groups of 48/12 healthy Europeans/Asians and 12 Europeans with pathological or incidental findings) using an 8Tx/32Rx head coil on a 7T whole-body MR system. Combined optimization values (COV) were defined as combination of spiral-nonselective (SPINS) trajectory parameters and an energy regularization weight. A set of COV was optimized universally by simulating the individual RF pulse optimizations of 12 training data sets (healthy Europeans). Subsequently, corresponding universal pulses (UPs) were calculated. Using COV and UPs, individually optimized pulses (IOPs) were calculated during the sequence preparation phase (maximum 15 s). Two different UPs and IOPs were evaluated by calculating their normalized root-mean-square error (NRMSE) of the FA and SAR in simulations of all data sets. Seven additional subjects were examined using an MPRAGE sequence that uses the designed pTx excitation pulses and a conventional adiabatic inversion. Results: All pTx pulses resulted in decreased mean NRMSE compared to a circularly polarized (CP) pulse (CP = 28%, UPs = 17%, and IOPs = 12%). UPs and IOPs improved homogeneity for all subjects. Differences in NRMSE between study groups were much lower than differences between different pulse types. Conclusion: UPs can be used to generate fast online-customized (FOCUS) pulses gaining lower NRMSE and/or lower SAR values.
CRIS-Team Scopus Importer:2021-01-15
Keywords: 7 T; k; parallel transmission (pTx); SPINS; ultra-high-field MRI; universal pulses

First German Guideline on Diagnostics and Therapy of Clinically Non-Functioning Pituitary Tumors - Deutschbein, Timo; Jaursch-Hancke, Cornelia; Knappe, Ulrich J.; Saeger, Wolfgang; Flitsch, Joerg; Bojunga, Joerg; Buchfelder, Michael; Ditzen, Beate; Gerlach, Ruediger; Gertzen, Elfriede; Honegger, Juergen; Horstmann, Gerhard A.; et al. (Experimental and Clinical Endocrinology and Diabetes, 2021)
Although non-functioning pituitary tumors are frequent, diagnostic and therapeutic concepts are not well standardized. We here present the first German multidisciplinary guideline on this topic. The single most important message is to manage the patients by a multidisciplinary team (consisting at least of an endocrinologist, a neurosurgeon, and a (neuro-) radiologist). The initial diagnostic work-up comprises a detailed characterization of both biochemical (focusing on hormonal excess or deficiency states) and morphological aspects (with magnetic resonance imaging of the sellar region). An ophthalmological examination is only needed in presence of symptoms or large tumors affecting the visual system. Asymptomatic, hormonally inactive tumors allow for a 'wait and scan' strategy. In contrast, surgical treatment by an experienced pituitary surgeon is standard of care in case of (impending) visual impairment. Therapeutic options for incompletely resected or recurrent tumors include re-operation, radiotherapy, and observation; the individual treatment plan should be developed multidisciplinary. Irrespective of the therapeutic approach applied, patients require long-term follow-up. Patient with larger pituitary tumors or former surgery/radiotherapy should be regularly counseled regarding potential symptoms of hormonal deficiency states.
CRIS-Team WoS Importer:2021-04-02

FLAIRfusion Processing with Contrast Inversion : Improving Detection and Reading Time of New Cerebral MS Lesions - Schmidt, Manuel; Linker, Ralf; Lang, S.; Lücking, Hannes; Engelhorn, Tobias; Kloska, Stephan; Uder, Michael; Dörfler, Arnd; Dankerl, Peter; Cavallaro, Alexander Josef (Clinical Neuroradiology, 2017)
To evaluate the performance of an innovative image processing approach for detection of T2-weighted hyperintense multiple sclerosis (MS) lesions.In this study 20 consecutive patients with inflammatory demyelinating lesions were retrospectively evaluated of whom 10 patients featured progressive disease and 10 a stable lesion load. 3 mm transversal FLAIRfusion imaging was processed and archived. Image processing was performed through landmark-based 3D co-registration of the previous and current isotropic FLAIR examination followed by inversion of image contrast. Thereby, the hyperintense signals of the unchanged MS plaques extinguish each other, while newly developed lesions appear bright on FLAIRfusion. Diagnostic performance was evaluated by 4 experienced readers. Consensus reading supplied the reference standard. Sensitivity, specificity, NPV (negative predictive value), PPV (positive predictive value), interreader agreement and reading time were the outcome measures analyzed.Combined sensitivity was 100% at a specificity of 88.2%, with PPV ranging from 83.3% to 90.1% and NPV at 100%. Reading time was nearly 5-fold faster than conventional side by side comparison (35.6 s vs. 163.7 s, p < 0.001). Cohen's kappa was excellent (>0.75; p < 0.001) and Cronbach's alpha was 0.994.FLAIRfusion provides reliable detection of newly developed MS lesions along with strong interreader agreement across all levels of expertise in 35 s of reading time.
EVALuna2:14615

Fluid suppression in amide proton transfer-weighted (APTw) CEST imaging: New theoretical insights and clinical benefits - Schüre, Jan-Rüdiger; Casagranda, Stefano; Sedykh, Maria; Liebig, Patrick; Papageorgakis, Christos; Mancini, Laura; Bisdas, Sotirios; Nichelli, Lucia; Pinter, Nandor; Mechtler, Laszlo; Jafari, Ramin; Boddaert, Nathalie; et al. (Magnetic Resonance in Medicine, 2023)
Purpose: Amide proton transfer-weighted (APTw) MRI at 3T provides a unique contrast for brain tumor imaging. However, APTw imaging suffers from hyperintensities in liquid compartments such as cystic or necrotic structures and provides a distorted APTw signal intensity. Recently, it has been shown that heuristically motivated fluid suppression can remove such artifacts and significantly improve the readability of APTw imaging. Theory and Methods: In this work, we show that the fluid suppression can actually be understood by the known concept of spillover dilution, which itself can be derived from the Bloch-McConnell equations in comparison to the heuristic approach. Therefore, we derive a novel post-processing formula that efficiently removes fluid artifact, and explains previous approaches. We demonstrate the utility of this APTw assessment in silico, in vitro, and in vivo in brain tumor patients acquired at MR scanners from different vendors. Results: Our results show a reduction of the CEST signals from fluid environments while keeping the APTw-CEST signal intensity almost unchanged for semi-solid tissue structures such as the contralateral normal appearing white matter. This further allows us to use the same color bar settings as for conventional APTw imaging. Conclusion: Fluid suppression has considerable value in improving the readability of APTw maps in the neuro-oncological field. In this work, we derive a novel post-processing formula from the underlying Bloch-McConnell equations that efficiently removes fluid artifact, and explains previous approaches which justify the derivation of this metric from a theoretical point of view, to reassure the scientific and medical field about its use.
CRIS-Team Scopus Importer:2023-12-22
Keywords: APTw CEST imaging; fluid suppression; MTRasym; post-processing

Frequent occurrence of therapeutically reversible CMV-associated encephalopathy during radiotherapy of the brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Ruehle, Paul F.; Putz, Florian; Semrau, Sabine; et al. (Neuro-Oncology, 2016)
Neurological decline during radio(chemo)therapy of the brain is often attributed to disease progression or side effects of radiotherapy. Diagnosis of opportunistic neurotropic infections such as cytomegalovirus (CMV) infections is uncommon, even though high-grade gliomas and some brain metastases are known to contain CMV particles. We prospectively examined the frequency of CMV encephalopathy during radiotherapy of the brain.Fifty patients requiring whole-brain radiotherapy for brain metastases (n = 27) or local radio(chemo)therapy of the brain for high-grade gliomas (n = 23) were observed in the prospective observational GLIO-CMV-01 study. MRIs and blood samples were obtained before, halfway through, and at the end of radiotherapy. MRIs were screened for disease progression or increased intracranial pressure. Blood was tested for anti-CMV immunoglobulin (Ig)M, anti-CMV IgG, and CMV DNA.Thirty-two of 50 (64%) patients were positive for anti-CMV IgG before radio(chemo)therapy. Fifteen of those 32 (48%) developed viremia during or up to 28 days after treatment. Thirteen of those 15 (87%) required treatment for CMV-associated encephalopathy. MRIs were negative for disease progression, edema, or bleeding. None of the patients negative for anti-CMV IgG developed viremia, suggesting a reactivation rather than a primary infection.In the group at risk consisting of anti-CMV IgG+ patients, age >65 (P = .004) and the amount of dexamethasone taken during radio(chemo)therapy (P = .004) were associated with an increased risk for CMV-associated encephalopathy. One hundred and fifty days after the start of radio(chemo)therapy, survival was 74% (14/19) (no encephalopathy) versus 54% (7/13) (encephalopathy) (odds ratio, 0.42; 95% CI, 0.03-1.86; P = .25).CMV reactivation frequently causes encephalopathy during radio(chemo)therapy of the brain. The unexpected high incidence of this infection makes it highly clinically relevant for every treating physician.
EVALuna2:8306

FSRT vs. SRS in Brain Metastases—Differences in Local Control and Radiation Necrosis—A Volumetric Study - Putz, Florian; Weissmann, Thomas; Oft, Dominik; Schmidt, Manuel; Roesch, Johannes; Siavooshhaghighi, Hadi; Filimonova, Irina; Schmitter, Charlotte; Mengling, Veit; Bert, Christoph; Frey, Benjamin; Lettmaier, Sebastian; et al. (Frontiers in Oncology, 2020)
Background: While the role of stereotactic radiotherapy for brain metastases is increasing, evidence on the comparative efficacy and safety of fractionated stereotactic radiotherapy (FSRT) and single-session radiosurgery (SRS) is scarce. Methods: Longitudinal volumetric analysis was performed in a consecutive cohort of 120 patients and 190 brain metastases (>0.065 cm3 in volume / > 5 mm in diameter) treated exclusively with FSRT (n = 98) and SRS (n = 92), respectively. A total of 972 tumor segmentations was used, averaging 5.1 time points per metastasis. Progression was defined using a volumetric extension of the RANO-BM criteria. Local control and radionecrosis were compared for lesions treated with FSRT and SRS, respectively. Results: Metastases treated with FSRT were significantly larger at baseline (mean, 4.66 vs. 0.40 cm3, p < 0.001). Biologically effective dose (BED) for metastases (α/β = 12, linear-quadratic-cubic model) was significantly associated with local control, whereas BED for normal brain (α/β = 2, linear-quadratic model) was significantly associated with radionecrosis. Median time to local progression was 22.9 months in the FSRT group compared to 14.5 months in the SRS group (p = 0.022). Overall radionecrosis rate at 12 months was 3.4% for FSRT and 14.8% for SRS (p = 0.010). Radionecrosis °IV requiring resection with histologic proof of radiation necrosis also was significantly reduced in the FSRT group (FSRT 0.0% vs. SRS 3.9%, p = 0.041). In multivariate analysis, FSRT was associated with reduced risk of progression (HR 0.47, p = 0.015) and reduced risk of radionecrosis (HR 0.18, p = 0.045). Conclusions: This volumetric study provides initial evidence that the improvements in therapeutic ratio expected for FSRT in larger brain metastases, might equally extend into the domain of smaller metastases, traditionally less considered for fractionated treatment. FSRT might constitute an important tool to further increase local control and reduce radionecrosis risk in stereotactic radiotherapy for brain metastases, that should be assessed in randomized intervention trials.
CRIS-Team Scopus Importer:2020-10-30
Keywords: brain metastases; fractionated stereotactic radiotherapy; radiobiological aspects; segmentation; stereotactic radiosurgery (SRS); stereotactic radiotherapy (SRT); volumetric analysis

High Detection Accuracy of an optimized 3D Convolutional Neural Network for Auto Detection and Auto Segmentation of Brain Metastases - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmitter, Charlotte; Semrau, Sabine; Lettmaier, Sebastian; Masitho, Siti; Grigo, Johanna; Schmidt, Manuel; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

High resolution time-of-flight MR-angiography at 7 T exploiting VERSE saturation, compressed sensing and segmentation - Meixner, Christian; Liebig, Patrick; Speier, Peter; Forman, Christoph; Hensel, Bernhard; Schmidt, Manuel; Saake, Marc; Uder, Michael; Dörfler, Arnd; Heidemann, Robin M.; Schmitter, Sebastian; Nagel, Armin Michael (Magnetic Resonance Imaging, 2019)
Background: 3D Time-of-Flight (TOF) MR-angiography (MRA) substantially benefits from ultra-high magnetic field strengths (≥7 T) due to increased Signal-to-Noise ratio and improved contrast. However, high-resolution TOF-MRA usually requires long acquisition times. In addition, specific absorption rate constraints limit the choice of optimal pulse sequence parameters, especially if venous saturation is employed. Purpose: To implement and evaluate an arterial TOF-MRA for accelerated high-resolution angiography at ultra-high magnetic field strength. Field strengths/sequence: 7 T modified gradient-echo TOF sequence including venous saturation using Variable-Rate Selective Excitation (VERSE), Compressed Sensing (CS) and sparse application of saturation pulses, called segmentation, were included for acceleration. Assessment: To analyze the acceleration techniques all volunteers were examined with the same protocols. CS with different sampling patterns and regularization factors as well as segmentation were applied for acceleration. For comparison, conventional acceleration techniques were applied (GRAPPA PAT 3 and Partial Fourier (6/8 in slice/phase encoding)). Images were co-registered and 40 mm thick transversal maximum intensity projections were created to calculate the relative number of vessels. To analyze the visibility of small vessels, the lenticulostriate arteries (LSA) were examined. This was done via multiscale vessel enhancement filtering in a VOI and quantification via Fiji ImageJ as well as qualitatively evaluation by two radiologists. Additionally, the venous/arterial vessel-to-background ratios (vVBR/aVBR) were calculated for chosen protocols. Results: For the acceleration of a high resolution TOF-MRA (0.31 mm isotropic), under-sampling of 9.6 showed aliasing artifacts, whereas 7.2 showed no aliasing. The regularization factor R had a strong impact on the image quality according to smoothing (R = 0.01 to R = 0.005) and noise (R = 0.0005 to R = 0.00005). With the alternating sampling patterns it was shown that the k-space center should not be under-sampled too much. Additionally segmentation could be verified to be feasible for stronger acceleration with sufficient venous suppression. Conclusion: The combination of several independent techniques (VERSE, CS with acceleration factor 7.2, R = 0.001, Poisson disc radius of 80%, 3 segments) enables the application of high-resolution (0.31 mm isotropic) TOF-MRA with venous saturation at 7 T in clinical time settings (TA ≈ 5 min) and within the SAR limits.
CRIS-Team Scopus Importer:2019-08-30
Keywords: 7 Tesla; Compressed sensing; MR-angiography; Time-of-flight; Ultra-high field; VERSE

Impairment of the Visual System in Glaucoma - Schmidt, Manuel; Engelhorn, Tobias; Dörfler, Arnd; Michelson, Georg (Klinische Monatsblätter für Augenheilkunde, 2019)
MR Diffusion Tensor Imaging (DTI) enables visualisation of the visual system in glaucoma; it has been shown that the atrophy of the optic radiation is more pronounced in glaucoma than in age-matched controls. The atrophy of the optic radiation thereby correlates with OCT and visual field measures. Diffusion tensor imaging permits quantification of the axonal integrity of the optic radiation by calculation of fractional anisotropy (FA) and radial diffusivity (RD). Both within and also outside the visual system, there are substantial changes in FA and RD, changes suggesting a complex neurodegenerative disease. Metabolic MRI by specific Na+-coils and by the CEST-technique (CEST: chemical exchange saturation transfer) will enable visualisation of neuronal cell death and pathological protein accumulation in the visual system. It is proposed that glaucomatous atrophy of the visual system may be induced by antero- and retrograde axonal degeneration. In normal tension glaucoma and PEX glaucoma, retrograde degeneration is induced by ischemic lesions or pathological protein accumulation within the cerebral portion of the visual system. Magnetic resonance imaging of the visual system with DTI and metabolic imaging will potentially improve therapeutic monitoring and diagnosis of glaucoma.
CRIS-Team WoS Importer:2019-03-06

Improved Detection of Cavernous Sinus Invasion of Pituitary Macroadenomas with Ultra-High-Field 7 T MRI - Eisenhut, Felix; Schmidt, Manuel; Buchfelder, Michael; Dörfler, Arnd; Schlaffer, Sven-Martin (Life, 2023)
To compare 7 T magnetic resonance imaging (MRI) of pituitary macroadenomas (PMA) with standard MRI and intraoperative findings regarding tumor detection, localization, size, and extension. Patients with suspected pituitary adenoma underwent pre-operative 1.5 T or 3 T and 7 T MRI; 14 patients with a PMA were included. A qualitative (lesion detection, location, cavernous sinus infiltration) and quantitative (lesion size, depth of cavernous sinus infiltration) analysis of 1.5 T, 3 T and 7 T MRI was performed and compared with intraoperative findings. Both 1.5/3 T and 7 T MRI enabled the detection of all PMAs; lesion size determination was equal. 7 T MRI enables more precise assessments of cavernous sinus infiltration of PMA (ncorrect 7T = 78.6%, ncorrect 1.5/3T = 64.3%). Ultra-high-field MRI is a reliable imaging modality for evaluation of PMAs providing exact information on lesion location and size. 7 T MRI yielded more accurate information on cavernous sinus infiltration with better agreement with intraoperative findings than standard MRI.
CRIS-Team Scopus Importer:2023-01-27
Keywords: cavernous sinus infiltration; intraoperative findings; pituitary macroadenoma; ultra-high-field MRI

Improved quantification in CEST-MRI by joint spatial total generalized variation - Huemer, Markus; Stilianu, Clemens; Maier, Oliver; Fabian, Moritz; Schmidt, Manuel; Dörfler, Arnd; Bredies, Kristian; Zaiß, Moritz; Stollberger, Rudolf (Magnetic Resonance in Medicine, 2024)
Purpose: In this work, the use of joint Total Generalized Variation (TGV) regularization to improve Multipool-Lorentzian fitting of chemical exchange saturation transfer (CEST) Spectra in terms of stability and parameter signal-to-noise ratio (SNR) was investigated. Theory and Methods: The joint TGV term was integrated into the nonlinear parameter fitting problem. To increase convergence and weight the gradients, preconditioning using a voxel-wise singular value decomposition was applied to the problem, which was then solved using the iteratively regularized Gauss–Newton method combined with a Primal-Dual splitting algorithm. The TGV method was evaluated on simulated numerical phantoms, 3T phantom data and 7T in vivo data with respect to systematic errors and robustness. Three reference methods were also implemented: The standard nonlinear fitting, a method using a nonlocal-means filter for denoising and the pyramid scheme, which uses downsampled images to acquire accurate start values. Results: The proposed regularized fitting method showed significantly improved robustness (compared to the reference methods). In testing, over a range of SNR values the TGV fit outperformed the other methods and showed accurate results even for large amounts of added noise. Parameter values found were closer or comparable to the ground truth. For in vivo datasets, the added regularization increased the parameter map SNR and prevented instabilities. Conclusion: The proposed fitting method using TGV regularization leads to improved results over a range of different data-sets and noise levels. Furthermore, it can be applied to all Z-spectrum data, with different amounts of pools, where the improved SNR and stability can increase diagnostic confidence.
CRIS-Team Scopus Importer:2024-07-26
Keywords: CEST; Lorentzian-fitting; rNOE; ssMT; TGV

Improvement of Deep Learning-based Auto-detection of Brain Metastases by Integrating previous MRI Images - Dörfler, Arnd; Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Maier, Andreas; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Investigation of lateral geniculate nucleus volume and diffusion tensor imaging in patients with normal tension glaucoma using 7 tesla magnetic resonance imaging - Schmidt, Manuel; Knott, Michael; Heidemann, Robin; Michelson, Georg; Kober, Tobias; Dörfler, Arnd; Engelhorn, Tobias (PLoS ONE, 2018)
BACKGROUND: There is evidence that glaucoma is a neurodegenerative disease involving the whole visual pathway. We prospectively examined potential benefits of volumetry of the lateral geniculate nucleus (LGN) and diffusion tensor imaging (DTI) using a new 7T scanner. METHODS: 20 patients with normal tension glaucoma and 16 control individuals were examined. LGN volume and fractional anisotropy (FA) of the optic tract (OT) and the optic radiation (OR) and their correlation with RNFL (retinal nerve fiber layer) thickness were analyzed. RESULTS: LGN volume was significantly reduced in NTG (60.9 vs 88.3; p < 0.05). FA of the OT (right: 0.35 vs 0.66, left: 0.36 vs 0.67; p < 0.05) and of the OR (right: 0.41 vs 0.70, left: 0.41 vs 0.69; p < 0.05) was also significantly reduced. Nasal RNFL thickness correlated with the volume of the contralateral LGN (r = 0.471, p = 0.05). Temporal RNFL thickness correlated with the volume of the ipsilateral LGN (r = 0.603, p = 0.015). CONCLUSION: NTG leads to significant atrophy of the LGN compared to controls. FA of the optic tract and the optic radiation is reduced in NTG as sign of axonal degeneration. RNFL thickness but not FA correlates with LGN volume.
EVALuna2:34502

Late-onset Krabbe disease presenting as spastic paraplegia – implications of GCase and CTSB/D - Mächtel, Rebecca; Dobert, Jan; Hehr, Ute; Weiß, Alexander; Kettwig, Matthias; Laugwitz, Lucia; Groeschel, Samuel; Schmidt, Manuel; Arnold, Philipp; Regensburger, Martin; Zunke, Friederike (Annals of Clinical and Translational Neurology, 2024)
Objective: Krabbe disease (KD) is a multisystem neurodegenerative disorder with severe disability and premature death, mostly with an infancy/childhood onset. In rare cases of late-onset phenotypes, symptoms are often milder and difficult to diagnose. We here present a translational approach combining diagnostic and biochemical analyses of a male patient with a progressive gait disorder starting at the age of 44 years, with a final diagnosis of late-onset KD (LOKD). Methods: Additionally to cerebral MRI, protein structural analyses of the β-galactocerebrosidase protein (GALC) were performed. Moreover, expression, lysosomal localization, and activities of β-glucocerebrosidase (GCase), cathepsin B (CTSB), and cathepsin D (CTSD) were analyzed in leukocytes, fibroblasts, and lysosomes of fibroblasts. Results: Exome sequencing revealed biallelic likely pathogenic variants: GALC exons 11–17: 33 kb deletion; exon 4: missense variant (c.334A>G, p.Thr112Ala). We detected a reduced GALC activity in leukocytes and fibroblasts. While histological KD phenotypes were absent in fibroblasts, they showed a significantly decreased activities of GCase, CTSB, and CTSD in lysosomal fractions, while expression levels were unaffected. Interpretation: The presented LOKD case underlines the age-dependent appearance of a mildly pathogenic GALC variant and its interplay with other lysosomal proteins. As GALC malfunction results in reduced ceramide levels, we assume this to be causative for the here described decrease in CTSB and CTSD activity, potentially leading to diminished GCase activity. Hence, we emphasize the importance of a functional interplay between the lysosomal enzymes GALC, CTSB, CTSD, and GCase, as well as between their substrates, and propose their conjoined contribution in KD pathology.
CRIS-Team Scopus Importer:2024-06-14
Keywords: cathepsin B; cathepsin D; enzymatic activity; Krabbe disease; late-onset; β-glucocerebrosidase

Linear projection-based CEST parameter estimation - Glang, Felix; Zaiss, Moritz; Laun, Frederik Bernd; Fabian, Moritz S.; German, Alexander; Khakzar, Katrin; Mennecke, Angelika; Liebert, Andrzej; Herz, Kai; Liebig, Patrick; Kasper, Burkhard S.; Schmidt, Manuel; et al. (NMR in Biomedicine, 2022)
Isolated evaluation of multi-parametric in vivo CEST MRI often requires complex computational processing for both correction of B0 and B1 inhomogeneity and contrast generation. For that, sufficiently densely sampled Z-spectra need to be acquired. The list of acquired frequency offsets largely determines the total CEST acquisition time, while potentially representing redundant information. In this work, a linear projection-based multi parametric CEST evaluation method is introduced that offers fast B0 and B1 inhomogeneity correction, contrast generation and feature selection for CEST data, enabling reduction of the overall measurement time. To that end, CEST data acquired at 7T in 6 healthy subjects and in one brain tumor patient were conventionally evaluated by interpolation-based inhomogeneity correction and Lorentzian curve fitting. Linear regression was used to obtain coefficient vectors that directly map uncorrected data to corrected Lorentzian target parameters. L1 regularization was applied to find subsets of the originally acquired CEST measurements that still allow for such a linear projection mapping. The linear projection method allows fast and interpretable mapping from acquired raw data to contrast parameters of interest, generalizing from healthy subject training data to unseen healthy test data and to the tumor patient dataset. The L1 regularization method shows that a fraction of the acquired CEST measurements is sufficient to preserve tissue contrasts, offering up to 2.8-fold reduction of scan time. Similar observations as for the 7T data can be made for data from a clinical 3T scanner. Being a fast and interpretable computation step, the proposed method is complementary to neural networks, which have been recently employed for similar purposes. The scan time acceleration offered by the L1 regularization (‘CEST-LASSO’) constitutes a step towards better applicability of multi parametric CEST protocols in clinical context.<br
Keywords: chemical exchange saturation transfer (CEST); feature selection; LASSO; APT; NOE; linear projection

Longitudinal Sodium MRI of Multiple Sclerosis Lesions: Is there Added Value of Sodium Inversion Recovery MRI - Mennecke, Angelika; Nagel, Armin Michael; Huhn, Konstantin; Linker, Ralf; Schmidt, Manuel; Rothhammer, Veit; Wilferth, Tobias; Linz, Peter; Wegmann, Julius; Eisenhut, Felix; Engelhorn, Tobias; Dörfler, Arnd (Journal of Magnetic Resonance Imaging, 2021)
Background Sodium enhancement has been demonstrated in multiple sclerosis (MS) lesions. Purpose To investigate sodium MRI with and without an inversion recovery pulse in acute MS lesions in an MS relapse and during recovery. Study Type Prospective. Subjects Twenty-nine relapsing-remitting MS patients with an acute relapse were included. Field Strength/Sequence A 3D density-adapted radial sodium sequence at 3 T using a dual-tuned (Na-23/H-1) head coil. Assessment Full-brain images of the tissue sodium concentration (TSC1, n = 29) and a sodium inversion recovery sequence (SIR1, n = 20) at the beginning of the anti-inflammatory therapy and on medium-term follow-up visits (days 27-99, n = 12 [TSC], n = 5 [SIR]) were measured. Regions of interest (RoIs) with contrast enhancement (T1CE+) and without change in T1-weighted imaging (FL + T1n) were normalized (nTSC and nSIR). To gain insight on the origin of the TSC enhancement at time point 1, it is investigated whether the nTSC enhancement of the lesions is accompanied by a change of the respective nSIR. Potential prognostic value of nSIR1 is examined referring to the nTSC progression. Statistical Tests nTSC and nSIR were compared regarding the type of lesion and the time point using a one-way ANOVA. Pearson's correlation coefficient was calculated for nTSC over nSIR and for nTSC1-nTSC2 over nSIR1. A P-value At the first measurement, all lesion types showed increased nTSC, while nSIR was decreased in the FL + T(1)n and the T1CE+ lesions in comparison to the normal-appearing white matter. For acute lesions, the difference between nTSC at baseline and nTSC at time point 2 showed a significant correlation with the baseline nSIR. Data Conclusion At time point 1, nTSC is increased, while nSIR is unchanged or decreased in the lesions. The mean sodium IR signal at baseline correlates with recovery or progression of an acute lesion. Evidence Level 2 Technical Efficacy Stage 4
CRIS-Team WoS Importer:2021-07-23

Magnetic resonance imaging for brain stereotactic radiotherapy - A review of requirements and pitfalls - Putz, Florian; Mengling, Veit; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Roesch, Johannes; Bäuerle, Tobias; Janka, Rolf Matthias; Uder, Michael; Amarteifio, Patrick; Doussin, Sylvain; Schmidt, Manuel; et al. (Strahlentherapie und Onkologie, 2020)
Due to its superior soft tissue contrast, magnetic resonance imaging (MRI) is essential for many radiotherapy treatment indications. This is especially true for treatment planning in intracranial tumors, where MRI has a long-standing history for target delineation in clinical practice. Despite its routine use, care has to be taken when selecting and acquiring MRI studies for the purpose of radiotherapy treatment planning. Requirements on MRI are particularly demanding for intracranial stereotactic radiotherapy, where accurate imaging has a critical role in treatment success. However, MR images acquired for routine radiological assessment are frequently unsuitable for high-precision stereotactic radiotherapy as the requirements for imaging are significantly different for radiotherapy planning and diagnostic radiology. To assure that optimal imaging is used for treatment planning, the radiation oncologist needs proper knowledge of the most important requirements concerning the use of MRI in brain stereotactic radiotherapy. In the present review, we summarize and discuss the most relevant issues when using MR images for target volume delineation in intracranial stereotactic radiotherapy.
CRIS-Team WoS Importer:2020-04-10

MR-zero meets RARE MRI: Joint optimization of refocusing flip angles and neural networks to minimize T2-induced blurring in spin echo sequences - Dang, Hoai Nam; Endres, Jonathan; Weinmüller, Simon; Glang, Felix; Loktyushin, Alexander; Scheffler, Klaus; Dörfler, Arnd; Schmidt, Manuel; Maier, Andreas; Zaiß, Moritz (Magnetic Resonance in Medicine, 2023)
Purpose: An end-to-end differentiable 2D Bloch simulation is used to reduce T2 induced blurring in single-shot turbo spin echo sequences, also called rapid imaging with refocused echoes (RARE) sequences, by using a joint optimization of refocusing flip angles and a convolutional neural network. Methods: Simulation and optimization were performed in the MR-zero framework. Variable flip angle train and DenseNet parameters were optimized jointly using the instantaneous transverse magnetization, available in our simulation, at a certain echo time, which serves as ideal blurring-free target. Final optimized sequences were exported for in vivo measurements at a real system (3 T Siemens, PRISMA) using the Pulseq standard. Results: The optimized RARE was able to successfully lower T2-induced blurring for single-shot RARE sequences in proton density-weighted and T2-weighted images. In addition to an increased sharpness, the neural network allowed correction of the contrast changes to match the theoretical transversal magnetization. The optimization found flip angle design strategies similar to existing literature, however, visual inspection of the images and evaluation of the respective point spread function demonstrated an improved performance. Conclusions: This work demonstrates that when variable flip angles and a convolutional neural network are optimized jointly in an end-to-end approach, sequences with more efficient minimization of T2-induced blurring can be found. This allows faster single- or multi-shot RARE MRI with longer echo trains.
CRIS-Team Scopus Importer:2023-07-07
Keywords: DenseNet; joint-optimization; MR-zero; RARE; RF-pulse design; T2-blurring; TSE

Multicenter privacy-preserving model training for deep learning brain metastases autosegmentation - Huang, Yixing; Khodabakhshi, Zahra; Gomaa, Ahmed; Schmidt, Manuel; Fietkau, Rainer; Guckenberger, Matthias; Andratschke, Nicolaus; Bert, Christoph; Tanadini-Lang, Stephanie; Putz, Florian (Radiotherapy and Oncology, 2024)
OBJECTIVES: This work aims to explore the impact of multicenter data heterogeneity on deep learning brain metastases (BM) autosegmentation performance, and assess the efficacy of an incremental transfer learning technique, namely learning without forgetting (LWF), to improve model generalizability without sharing raw data. MATERIALS AND METHODS: A total of six BM datasets from University Hospital Erlangen (UKER), University Hospital Zurich (USZ), Stanford, UCSF, New York University (NYU), and BraTS Challenge 2023 were used. First, the performance of the DeepMedic network for BM autosegmentation was established for exclusive single-center training and mixed multicenter training, respectively. Subsequently privacy-preserving bilateral collaboration was evaluated, where a pretrained model is shared to another center for further training using transfer learning (TL) either with or without LWF. RESULTS: For single-center training, average F1 scores of BM detection range from 0.625 (NYU) to 0.876 (UKER) on respective single-center test data. Mixed multicenter training notably improves F1 scores at Stanford and NYU, with negligible improvement at other centers. When the UKER pretrained model is applied to USZ, LWF achieves a higher average F1 score (0.839) than naive TL (0.570) and single-center training (0.688) on combined UKER and USZ test data. Naive TL improves sensitivity and contouring accuracy, but compromises precision. Conversely, LWF demonstrates commendable sensitivity, precision and contouring accuracy. When applied to Stanford, similar performance was observed. CONCLUSION: Data heterogeneity (e.g., variations in metastases density, spatial distribution, and image spatial resolution across centers) results in varying performance in BM autosegmentation, posing challenges to model generalizability. LWF is a promising approach to peer-to-peer privacy-preserving model training.
EVALuna2:587588
Keywords: Continual learning; Learning without forgetting; Brain metastasis; Multicenter collaboration; Data privacy; Data heterogeneity

Neurometabolic Dysfunction in SPG11 Hereditary Spastic Paraplegia. - Winner, Beate; Marterstock, Dominique; Kopp, Christoph; Dörfler, Arnd; Regensburger, Martin; Krumm, Laura; Schmidt, Manuel; Schmid, Andreas; Spatz, Imke; Marterstock, Dominique; Kopp, Christoph; Kohl, Zacharias; et al. (Nutrients, 2022)
Body composition, adipokine levels, and hypothalamic volume are altered in SPG11. Our data indicate a link between obesity and hypothalamic neurodegeneration in SPG11 and imply that specific metabolic interventions may prevent obesity despite severely impaired mobility in SPG11. Pathogenic variants in SPG11 cause the most common autosomal recessive complicated hereditary spastic paraplegia. Besides the prototypical combination of spastic paraplegia with a thin corpus callosum, obesity has increasingly been reported in this multisystem neurodegenerative disease. However, a detailed analysis of the metabolic state is lacking. In order to characterize metabolic alterations, a cross-sectional analysis was performed comparing SPG11 patients (n = 16) and matched healthy controls (n = 16). We quantified anthropometric parameters, body composition as determined by bioimpedance spectroscopy, and serum metabolic biomarkers, and we measured hypothalamic volume by high-field MRI. Compared to healthy controls, SPG11 patients exhibited profound changes in body composition, characterized by increased fat tissue index, decreased lean tissue index, and decreased muscle mass. The presence of lymphedema correlated with increased extracellular fluid. The serum levels of the adipokines leptin, resistin, and progranulin were significantly altered in SPG11 while adiponectin and C1q/TNF-related protein 3 (CTRP-3) were unchanged. MRI volumetry revealed a decreased hypothalamic volume in SPG11 patients. CONCLUSIONS BACKGROUND METHODS RESULTS
Keywords: SPG11; adipokines; bioimpedance spectroscopy; hypothalamus; leptin; obesity

Neuropsychology and MRI correlates of neurodegeneration in SPG11 hereditary spastic paraplegia - Utz, Kathrin; Kohl, Zacharias; Marterstock, Dominique; Dörfler, Arnd; Winkler, Jürgen; Schmidt, Manuel; Regensburger, Martin (Orphanet Journal of Rare Diseases, 2022)
Background: SPG11-linked hereditary spastic paraplegia is characterized by multisystem neurodegeneration leading to a complex clinical and yet incurable phenotype of progressive spasticity and weakness. Severe cognitive symptoms are present in the majority of SPG11 patients, but a systematic and multidimensional analysis of the neuropsychological phenotype in a larger cohort is lacking. While thinning of the corpus callosum is a well-known structural hallmark observed in SPG11 patients, the neuroanatomical pattern of cortical degeneration is less understood. We here aimed to integrate neuropsychological and brain morphometric measures in SPG11. Methods: We examined the neuropsychological profile in 16 SPG11 patients using a defined neuropsychological testing battery. Long-term follow up testing was performed in 7 patients. Cortical and subcortical degeneration was analyzed using an approved, artificial intelligence based magnetic resonance imaging brain morphometry, comparing patients to established reference values and to matched controls. Results: In SPG11 patients, verbal fluency and memory as well as frontal-executive functions were severely impaired. Later disease stages were associated with a global pattern of impairments. Interestingly, reaction times correlated significantly with disease progression. Brain morphometry showed a significant reduction of cortical and subcortical parenchymal volume following a rostro-caudal gradient in SPG11. Whereas performance in memory tasks correlated with white matter damage, verbal fluency measures showed strong associations with frontal and parietal cortical volumes. Conclusions: The present data will help define neuropsychological and imaging read out parameters in early as well as in advanced clinical stages for future interventional trials in SPG11.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Brain morphometry; Neuropsychology; Spastic paraplegia; SPG11; Verbal fluency

No evidence of disease activity status over 3 years in a real-world cohort of relapsing remitting MS patients in Germany - Huhn, Konstantin; Senger, Daniela; Utz, Kathrin S.; Schmidt, Manuel; Fröhlich, Katharina; Waschbisch, Anne; Seifert, Frank; Dörfler, Arnd; Lee, De-Hyung; Linker, Ralf A. (Multiple Sclerosis and Related Disorders, 2019)
BACKGROUND: Over the last decade, therapy of relapsing remitting multiple sclerosis (RRMS) has evolved with the approval of several new treatment concepts. Thus, treatment goals have become more ambitious aiming at "no evidence of disease activity" (NEDA). As NEDA-3, this concept comprises freedom of clinical disease progression and relapses as well as inflammatory MRI activity. So far, data on NEDA status mainly stem from post-hoc analyses of drug approval studies. Yet, less is known about the significance of NEDA in "real-world" clinical settings. Hence, our study aims at investigation of NEDA in a heterogeneous cohort of relapsing MS patients. METHODS: This is a retrospective single-center study at the Department of Neurology of the University Hospital Erlangen, Germany, including data of 306 patients with relapsing forms of MS (RMS) or clinical isolated syndrome (CIS) from 2009 to 2016. Inclusion required sufficient clinical information and in house cranial MRI follow-up data sets at baseline and at follow-up after one year with a potential extension to two and three year follow-up, if possible. NEDA-3 status, its correlation to clinical features, associated medication and NEDA failure (EDA) were analyzed. RESULTS: In a cohort of RMS patients at the early stages of the disease (median EDSS 1.5, mean disease duration 30 months) at baseline, 45% retained NEDA-3 status after one year. This percentage decreased in year two (29%) and three (21%) of follow-up. MRI criteria were responsible for loss of NEDA status in 64% of cases and CIS patients were more likely to sustain NEDA status. Therapy with monoclonal antibodies appeared superior in sustaining NEDA status as compared to injectables or oral treatment options. DISCUSSION: In our real-world analysis, we confirm the potential of NEDA for the evaluation and surveillance of MS disease activity, progression and therapy efficacy. Despite highly efficient immunomodulatory treatment, NEDA-3 was only preserved in a minority of patients. Monoclonal antibodies may yield best NEDA rates. Further studies are warranted to evaluate the value of the NEDA concept in real-world settings beyond standardized clinical studies.
EVALuna2:36277

Nonparametric D-R1-R2 distribution MRI of the living human brain - Laun, Frederik Bernd; Martin, Jan; Reymbaut, Alexis; Schmidt, Manuel; Dörfler, Arnd; Topgaard, Daniel; Uder, Michael (2021)
Diffusion-relaxation correlation NMR can simultaneously characterize both the microstructure and the local chemical composition of complex samples that contain multiple populations of water. Recent developments on tensor-valued diffusion encoding and Monte Carlo inversion algorithms have made it possible to transfer diffusion-relaxation correlation NMR from small-bore scanners to clinical MRI systems. Initial studies on clinical MRI systems employed 5D D-R1 and D-R2 correlation to characterize healthy brain in vivo. However, these methods are subject to an inherent bias that originates from not including R2 or R1 in the analysis, respectively. This drawback can be remedied by extending the concept to 6D D-R1-R2 correlation. In this work, we present a sparse acquisition protocol that records all data necessary for in vivo 6D D-R1-R2 correlation MRI across 633 individual measurements within 25 min—a time frame comparable to previous lower-dimensional acquisition protocols. The data were processed with a Monte Carlo inversion algorithm to obtain nonparametric 6D D-R1-R2 distributions. We validated the reproducibility of the method in repeated measurements of healthy volunteers. For a post-therapy glioblastoma case featuring cysts, edema, and partially necrotic remains of tumor, we present representative single-voxel 6D distributions, parameter maps, and artificial contrasts over a wide range of diffusion-, R1-, and R2-weightings based on the rich information contained in the D-R1-R2 distributions.
CRIS-Team Scopus Importer:2021-12-10
Keywords: Correlation; Diffusion; Microstructure; Relaxation; Signal inversion

Novel Homozygous FA2H Variant Causing the Full Spectrum of Fatty Acid Hydroxylase-Associated Neurodegeneration (SPG35) - German, Alexander; Jukic, Jelena; Laner, Andreas; Arnold, Philipp; Socher, Eileen; Mennecke, Angelika; Schmidt, Manuel; Winkler, Jürgen; Abicht, Angela; Regensburger, Martin (Genes, 2023)
Fatty acid hydroxylase-associated neurodegeneration (FAHN/SPG35) is caused by pathogenic variants in FA2H and has been linked to a continuum of specific motor and non-motor neurological symptoms, leading to progressive disability. As an ultra-rare disease, its mutational spectrum has not been fully elucidated. Here, we present the prototypical workup of a novel FA2H variant, including clinical and in silico validation. An 18-year-old male patient presented with a history of childhood-onset progressive cognitive impairment, as well as progressive gait disturbance and lower extremity muscle cramps from the age of 15. Additional symptoms included exotropia, dystonia, and limb ataxia. Trio exome sequencing revealed a novel homozygous c.75C>G (p.Cys25Trp) missense variant in the FA2H gene, which was located in the cytochrome b5 heme-binding domain. Evolutionary conservation, prediction models, and structural protein modeling indicated a pathogenic loss of function. Brain imaging showed characteristic features, thus fulfilling the complete multisystem neurodegenerative phenotype of FAHN/SPG35. In summary, we here present a novel FA2H variant and provide prototypical clinical findings and structural analyses underpinning its pathogenicity.<br
Keywords: hereditary spastic paraplegia; SPG35; FA2H; FAHN; genetic variant modeling

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

Parkinson's disease or multiple system atrophy: potential separation by quantitative susceptibility mapping - Marxreiter, Franz; Lambrecht, Vera; Mennecke, Angelika; Hanspach, Jannis; Jukic, Jelena; Regensburger, Martin; Herrler, Jürgen; German, Alexander; Kassubek, Jan; Groen, Georg; Mueller, Hans-Peter; Laun, Frederik Bernd; et al. (Therapeutic Advances in Neurological Disorders, 2023)
Background:Due to the absence of robust biomarkers, and the low sensitivity and specificity of routine imaging techniques, the differential diagnosis between Parkinson's disease (PD) and multiple system atrophy (MSA) is challenging. High-field magnetic resonance imaging (MRI) opened up new possibilities regarding the analysis of pathological alterations associated with neurodegenerative processes. Recently, we have shown that quantitative susceptibility mapping (QSM) enables visualization and quantification of two major histopathologic hallmarks observed in MSA: reduced myelin density and iron accumulation in the basal ganglia of a transgenic murine model of MSA. It is therefore emerging as a promising imaging modality on the differential diagnosis of Parkinsonian syndromes. Objectives:To assess QSM on high-field MRI for the differential diagnosis of PD and MSA. Methods:We assessed 23 patients (nine PDs and 14 MSAs) and nine controls using QSM on 3T and 7T MRI scanners at two academic centers. Results:We observed increased susceptibility in MSA at 3T in prototypical subcortical and brainstem regions. Susceptibility measures of putamen, pallidum, and substantia nigra reached excellent diagnostic accuracy to separate both synucleinopathies. Increase toward 100% sensitivity and specificity was achieved using 7T MRI in a subset of patients. Magnetic susceptibility correlated with age in all groups, but not with disease duration in MSA. Sensitivity and specificity were particularly high for possible MSA, and reached 100% in the putamen. Conclusion:Putaminal susceptibility measures, in particular on ultra-high-field MRI, may distinguish MSA patients from both, PD and controls, allowing an early and sensitive diagnosis of MSA.
CRIS-Team WoS Importer:2023-03-17

PASSED: Brain atrophy in non-demented individuals in a long-term longitudinal study from two independent cohorts - Haas, Anna-Lena; Olm, Pauline; Utz, Janine; Siegmann, Eva-Maria; Spitzer, Philipp; Florvaag, Anna; Schmidt, Manuel; Dörfler, Arnd; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo (Frontiers in Aging Neuroscience, 2023)
Introduction: Alzheimer’s disease (AD) is indicated by a decrease in amyloid beta 42 (Aβ42) level or the Aβ42/Aβ40 ratio, and by increased levels of Tau with phosphorylated threonine at position 181 (pTau181) in cerebrospinal fluid (CSF) years before the onset of clinical symptoms. However, once only pTau181 is increased, cognitive decline in individuals with subjective or mild cognitive impairment is slowed compared to individuals with AD. Instead of a decrease in Aβ42 levels, an increase in Aβ42 was observed in these individuals, leading to the proposal to refer to them as nondemented subjects with increased pTau-levels and Aβ surge with subtle cognitive deterioration (PASSED). In this study, we determined the longitudinal atrophy rates of AD, PASSED, and Biomarker-negative nondemented individuals of two independent cohorts to determine whether these groups can be distinguished by their longitudinal atrophy patterns or rates. Methods: Depending on their CSF-levels of pTau 181 (T), total Tau (tTau, N), Aβ42 or ratio of Aβ42/Aβ40 (A), 185 non-demented subjects from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and 62 non-demented subjects from Erlangen AD cohort were assigned to an ATN group (A–T–N–, A–T+N±, A+T–N±and A+T+N±) and underwent T1-weighted structural magnetic resonance imaging (sMRI). Longitudinal grey matter (GM) atrophy patterns were assessed with voxel-based morphometry (VBM) using the cat12 toolbox on spm12 (statistical parametric mapping) of MRI scans from individuals in the ADNI cohort with a mean follow-up of 2 and 5 years, respectively. The annualized atrophy rate for individuals in the Erlangen cohort was determined using region of interest analysis (ROI) in terms of a confirmatory analysis. Results: In the A–T+N± group, VBM did not identify any brain region that showed greater longitudinal atrophy than the A+T+N±, A+T+N± or biomarker negative control group. In contrast, marked longitudinal atrophy in the temporal lobe was evident in the A+T–N± group compared with A+T–N± and biomarker-negative subjects. The ROI in the angular gyrus identified by VBM analysis of the ADNI cohort did not discriminate better than the hippocampal volume and atrophy rate between AD and PASSED in the confirmatory analysis. Discussion: In this study, nondemented subjects with PASSED did not show a unique longitudinal atrophy pattern in comparison to nondemented subjects with AD. The nonsignificant atrophy rate compared with controls suggests that increased pTau181-levels without concomitant amyloidopathy did not indicate a neurodegenerative disorder.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Alzheimer disease/physiopathology*; amyloid beta-peptides/cerebrospinal fluid*; ATN classification; longitudinal studies; magnetic resonance imaging; medial temporal lobe; SNAP; tau proteins/cerebrospinal fluid*

Physics-Informed Conditional Autoencoder Approach for Robust Metabolic CEST MRI at 7T - Rajput, Junaid R.; Möhle, Tim A.; Fabian, Moritz; Mennecke, Angelika; Sembill, Jochen; Kuramatsu, Joji; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Zaiß, Moritz (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2023)
Chemical exchange saturation transfer (CEST) is an MRI method that provides insights on the metabolic level. Several metabolite effects appear in the CEST spectrum. These effects are isolated by Lorentzian curve fitting. The separation of CEST effects suffers from the inhomogeneity of the saturation field B1. This leads to inhomogeneities in the associated metabolic maps. Current B1 correction methods require at least two sets of CEST-spectra. This at least doubles the acquisition time. In this study, we investigated the use of an unsupervised physics-informed conditional autoencoder (PICAE) to efficiently correct B1 inhomogeneity and isolate metabolic maps while using a single CEST scan. The proposed approach integrates conventional Lorentzian model into the conditional autoencoder and performs voxel-wise B1 correction and Lorentzian line fitting. The method provides clear interpretation of each step and is inherently generative. Thus, CEST-spectra and fitted metabolic maps can be created at arbitrary B1 levels. This is important because the B1 dispersion contains information about the exchange rates and concentration of metabolite protons, paving the way for their quantification. The isolated maps for tumor data showed a robust B1 correction and more than 25% increase in structural similarity index (SSIM) with gadolinium reference image compared to the standard interpolation-based method and subsequent Lorentzian curve fitting. This efficient correction method directly results in at least 50% reduction in scan time.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Acquisition time; Bound loss; CEST; Interpretability; Lorentzian fit; Physics-informed autoencoder

Prospective intraindividual comparison of gadoterate and gadobutrol for cervical and intracranial contrast-enhanced magnetic resonance angiography - Lang, Stefan; Weibart, Marina; Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Essig, Marco; Kloska, Stephan; Dörfler, Arnd; Hölter, Philip (Neuroradiology, 2017)
PURPOSE: Gadobutrol (GB) is reported to provide improved relaxivity and concentration compared to gadoterate (GT). This study was designed to intraindividually compare quantitative and qualitative enhancement characteristics of GB to GT in cervicocranial magnetic resonance angiography (MRA) of patients with cerebrovascular disease (CVD). METHODS: Patients (n = 54) with CVD underwent two identical contrast-enhanced magnetic resonance angiography (CE-MRA) examinations of the cervical and intracranial vasculature in randomized order, using GB and GT in equimolar dose. Signal-to-noise ratios (SNR) and contrast-to-noise ratios (CNR) were obtained by two independent neuroradiologists, blinded to the applied contrast agents. Qualitative assessment was performed using a three-point scale with a focus on M1/M2 segments. RESULTS: One thousand and twenty-six vessel segments were analyzed. GB revealed a significantly higher SNR (p = 0.032) and CNR (p = 0.031) in all vessel segments. GB featured a significantly higher SNR and CNR in thoracic (p = 0.022; p = 0.016) and cervical vessels (p = 0.03; p = 0.038), as well as in the posterior circulation (p = 0.012; p = 0.005). In blinded qualitative assessment, overall preference was given to GB (p = 0.02), showing a significant better delineation of the M1/M2 segments (p = 0.041). CONCLUSION: Compared to GT, the use of GB results in a significantly higher SNR and CNR in cervical and cerebral CE-MRA, leading to a better delineation of the intracranial vasculature. Present results underline the potential of GB for improved CE-MRA assessment of vasculature in CVD patients.
EVALuna2:33134

Pulsed Arterial Spin Labeling and Segmented Brain Volumetry in the Diagnostic Evaluation of Frontotemporal Dementia, Alzheimer’s Disease and Mild Cognitive Impairment - Marterstock, Dominique; Knott, Michael; Lang, Stefan; Oberstein, Timo; Kornhuber, Johannes; Dörfler, Arnd; Schmidt, Manuel; Hölter, Philip (Tomography, 2022)
Background: Previous studies suggest that brain atrophy can not only be defined by its morphological extent, but also by the cerebral blood flow (CBF) within a certain area of the brain, including white and gray matter. The aim of this study is to investigate known atrophy patterns in different forms of dementia and to compare segmented brain volumetrics and pulsed arterial spin labeling (pASL) data to explore the correlation between brain maps with atrophy and this non-contrast-enhanced brain-perfusion method. Methods: Our study comprised 17 patients with diagnosed cognitive impairment (five Alzheimer’s disease = AD, five frontotemporal dementia = FTD, seven mild cognitive impairment = MCI) and 19 healthy control subjects (CO). All patients and controls underwent 4D-pASL brain-perfusion MR imaging and T1w MPRAGE. The data were assessed regarding relative brain volume on the basis of 286 brain regions, and absolute and relative cerebral blood flow (CBF/rCBF) were derived from pASL data in the corresponding brain regions. Mini-Mental State Examination (MMSE) was performed to assess cognitive functions. Results: FTD patients demonstrated significant brain atrophy in 43 brain regions compared to CO. Patients with MCI showed significant brain atrophy in 18 brain regions compared to CO, whereas AD patients only showed six brain regions with significant brain atrophy compared to CO. There was good correlation of brain atrophy and pASL perfusion data in five brain regions of patients with diagnosed FTD, especially in the superior temporal gyrus (r = 0.900, p = 0.037), the inferior frontal white matter (pars orbitalis; r = 0.968, p = 0.007) and the thalami (r = 0.810, p = 0.015). Patients with MCI demonstrated a correlation in one brain region (left inferior fronto-occipital fasciculus; r = 0.786, p = 0.036), whereas patients with diagnosed AD revealed no correlation. Conclusions: pASL can detect affected brain regions in cognitive impairment and corresponds with brain atrophy, especially for patients suffering from FTD and MCI. However, there was no correlation of perfusion alterations and brain atrophy in AD. pASL perfusion might thus represent a promising tool for noninvasive brain-perfusion evaluation in specific dementia subtypes as a complimentary imaging-based bio marker in addition to brain volumetry.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alzheimer’s disease; Brain volumetry; Dementia; Frontotemporal dementia; Mild cognitive impairment; Pulsed arterial spin labeling

Pulseq-CEST: Towards multi-site multi-vendor compatibility and reproducibility of CEST experiments using an open-source sequence standard - Herz, Kai; Mueller, Sebastian; Perlman, Or; Zaitsev, Maxim; Knutsson, Linda; Sun, Phillip Zhe; Zhou, Jinyuan; Van Zijl, Peter; Heinecke, Kerstin; Schuenke, Patrick; Farrar, Christian T.; Schmidt, Manuel; et al. (Magnetic Resonance in Medicine, 2021)
Purpose As the field of CEST grows, various novel preparation periods using different parameters are being introduced. At the same time, large, multisite clinical studies require clearly defined protocols, especially across different vendors. Here, we propose a CEST definition standard using the open Pulseq format for a shareable, simple, and exact definition of CEST protocols.
CRIS-Team WoS Importer:2021-05-28

Quality assurance guidelines for interstitial hyperthermia - Trefna, H. Dobsicek; Schmidt, Manuel; Van Rhoon, G. C.; Kok, H. P.; Gordeyev, S. S.; Lamprecht, U.; Marder, D.; Nadobny, J.; Ghadjar, P.; Abdel-Rahman, S.; Kukielka, A. M.; Strnad, Vratislav; et al. (International Journal of Hyperthermia, 2019)
Quality assurance (QA) guidelines are essential to provide uniform execution of clinical hyperthermia treatments and trials. This document outlines the clinical and technical consequences of the specific properties of interstitial heat delivery and specifies recommendations for hyperthermia administration with interstitial techniques. Interstitial hyperthermia aims at tumor temperatures in the 40-44 degrees C range as an adjunct to radiation or chemotherapy. The clinical part of this document imparts specific clinical experience of interstitial heat delivery to various tumor sites as well as recommended interstitial hyperthermia workflow and procedures. The second part describes technical requirements for quality assurance of current interstitial heating equipment including electromagnetic (radiative and capacitive) and ultrasound heating techniques. Detailed instructions are provided on characterization and documentation of the performance of interstitial hyperthermia applicators to achieve reproducible hyperthermia treatments of uniform high quality. Output power and consequent temperature rise are the key parameters for characterization of applicator performance in these QA guidelines. These characteristics determine the specific maximum tumor size and depth that can be heated adequately. The guidelines were developed by the ESHO Technical Committee with participation of senior STM members and members of the Atzelsberg Circle.
CRIS-Team WoS Importer:2019-04-09

Quality requirements for MRI simulation in cranial stereotactic radiotherapy: a guideline from the German Taskforce “Imaging in Stereotactic Radiotherapy” - Putz, Florian; Bock, Michael; Schmitt, Daniela; Bert, Christoph; Blanck, Oliver; Ruge, Maximilian I.; Hattingen, Elke; Karger, Christian P.; Fietkau, Rainer; Grigo, Johanna; Schmidt, Manuel; Bäuerle, Tobias; et al. (Strahlentherapie und Onkologie, 2024)
Accurate Magnetic Resonance Imaging (MRI) simulation is fundamental for high-precision stereotactic radiosurgery and fractionated stereotactic radiotherapy, collectively referred to as stereotactic radiotherapy (SRT), to deliver doses of high biological effectiveness to well-defined cranial targets. Multiple MRI hardware related factors as well as scanner configuration and sequence protocol parameters can affect the imaging accuracy and need to be optimized for the special purpose of radiotherapy treatment planning. MRI simulation for SRT is possible for different organizational environments including patient referral for imaging as well as dedicated MRI simulation in the radiotherapy department but require radiotherapy-optimized MRI protocols and defined quality standards to ensure geometrically accurate images that form an impeccable foundation for treatment planning. For this guideline, an interdisciplinary panel including experts from the working group for radiosurgery and stereotactic radiotherapy of the German Society for Radiation Oncology (DEGRO), the working group for physics and technology in stereotactic radiotherapy of the German Society for Medical Physics (DGMP), the German Society of Neurosurgery (DGNC), the German Society of Neuroradiology (DGNR) and the German Chapter of the International Society for Magnetic Resonance in Medicine (DS-ISMRM) have defined minimum MRI quality requirements as well as advanced MRI simulation options for cranial SRT.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Brain metastases; DEGRO; DGMP; DGNC; DGNR; DS-ISMRM; Guideline; Meningioma; MRI simulation; Pituitary adenoma; Stereotactic radiosurgery; Stereotactic radiotherapy; Trigeminal neuralgia; Vestibular schwannoma

Quantitative 7T sodium magnetic resonance imaging of the human brain using a 32-channel phased-array head coil: Application to patients with secondary progressive multiple sclerosis - Wilferth, Tobias; Mennecke, Angelika; Gast, Lena; Lachner, Sebastian; Müller, Max; Rothhammer, Veit; Huhn, Konstantin; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael; Schmidt, Manuel (NMR in Biomedicine, 2022)
Apparent tissue sodium concentrations (aTSCs) determined by 23Na brain magnetic resonance imaging (MRI) have the potential to serve as a biomarker in pathologies such as multiple sclerosis (MS). However, the quantification is hindered by the intrinsically low signal-to-noise ratio of 23Na MRI. The purpose of this study was to improve the accuracy and reliability of quantitative 23Na brain MRI by implementing a dedicated postprocessing pipeline and to evaluate the applicability of the developed approach for the examination of MS patients. 23Na brain MRI measurements of 13 healthy volunteers and 17 patients with secondary progressive multiple sclerosis (SPMS) were performed at 7 T using a dual-tuned 23Na/1H birdcage coil with a receive-only 32-channel phased array. The aTSC values were determined for normal appearing white matter (NAWM) and normal appearing gray matter (NAGM) in healthy subjects and SPMS patients. Signal intensities were normalized using the mean cerebrospinal fluid (CSF) sodium concentration determined in 37 separate patients receiving a spinal tap for routine diagnostic purposes. Five volunteers underwent MRI examinations three times in a row to assess repeatability. Coefficients of variation (CoVs) were used to quantify the repeatability of the proposed method. aTSC values were compared regarding brain regions and subject cohort using the paired-samples Wilcoxon rank-sum test. Laboratory CSF sodium concentration did not differ significantly between patients without and with MS (p = 0.42). The proposed quantification workflow for 23Na MRI was highly repeatable with CoVs averaged over all five volunteers of 1.9% ± 0.9% for NAWM and 2.2% ± 1.6% for NAGM. Average NAWM aTSC was significantly higher in patients with SPMS compared with the control group (p = 0.009). Average NAGM aTSC did not differ significantly between healthy volunteers and MS patients (p = 0.98). The proposed postprocessing pipeline shows high repeatability and the results can serve as a baseline for further studies establishing 23Na brain MRI as a biomarker in diseases such as MS.
CRIS-Team Scopus Importer:2022-08-19
Keywords: 7 T; brain MRI; multiple sclerosis

Quantitative and qualitative comparison of 4D-DSA with 3D-DSA using computational fluid dynamics simulations in cerebral aneurysms - Lang, Sabine; Birkhold, A. I.; Schmidt, Manuel; Endres, J.; Strother, C.; Dörfler, Arnd; Lücking, Hannes; Hölter, Philip (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: 4D-DSA allows time-resolved 3D imaging of the cerebral vasculature. The aim of our study was to evaluate this method in comparison with the current criterion standard 3D-DSA by qualitative and quantitative means using computational fluid dynamics. MATERIALS AND METHODS: 3D- and 4D-DSA datasets were acquired in patients with cerebral aneurysms. Computational fluid dynamics analysis was performed for all datasets. Using computational fluid dynamics, we compared 4D-DSA with 3D-DSA in terms of both aneurysmal geometry (quantitative: Maximum diameter, ostium size [OZ1/2], volume) and hemodynamic parameters (qualitative: Flow stability, flow complexity, inflow concentration; quantitative: Average/maximum wall shear stress, impingement zone, low-stress zone, intra-aneurysmal pressure, and flow velocity). Qualitative parameters were descriptively analyzed. Correlation coefficients (r, P value) were calculated for quantitative parameters. RESULTS: 3D- and 4D-DSA datasets of 10 cerebral aneurysms in 10 patients were postprocessed. Evaluation of aneurysmal geometry with 4D-DSA (rmaximum diameter = 0.98, Pmaximum diameter <.001; rOZ1/OZ2 = 0.98/0.86, POZ1/OZ2 =.001/.002; rvolume = 0.98, Pvolume <.001) correlated highly with 3D-DSA. Evaluation of qualitative hemodynamic parameters (flow stability, flow complexity, inflow concentration) did show complete accordance, and evaluation of quantitative hemodynamic parameters (raverage/maximum wall shear stress diastole=0.92/0.88, Paverage/maximum wall shear stress diastole <.001/.001; raverage/maximum wall shear stress systole = 0.94/0.93, Paverage/maximum wall shear stress systole < .001/.001; rimpingement zone=0.96, Pimpingement zone <.001; rlow-stress zone=1.00, Plow-stress zone <.01; rpressure diastole=0.84,Ppressure diastole< .002; rpressure systole=0.9, Ppressure systole <.001; rflow velocity diastole=0.95, Pflow velocity diastole <.001; rflow velocity systole=0.93,Pflow velocity systole <.001) did show nearly complete accordance between 4D- and 3D-DSA. CONCLUSIONS: Despite a different injection protocol, 4D-DSA is a reliable basis for computational fluid dynamics analysis of the intracranial vasculature and provides equivalent visualization of aneurysm geometry compared with 3D-DSA.
CRIS-Team Scopus Importer:2019-09-17

Quantitative Corticospinal Tract Assessment in Acute Intracerebral Hemorrhage - Volbers, Bastian; Mennecke, Angelika; Kästle, Nicola; Huttner, Hagen; Schwab, Stefan; Schmidt, Manuel; Engelhorn, Tobias Martin; Dörfler, Arnd (Translational Stroke Research, 2020)
Intracerebral hemorrhage (ICH) prognostication during the acute phase is often subjective among physicians and often affects treatment decisions. The present study explores objective imaging parameters using quantitative corticospinal tract (CST) fiber reconstruction during the acute phase of ICH and correlates these parameters with functional outcome and patient recovery. We prospectively enrolled nonsurgical spontaneous supratentorial ICH patients and obtained an MRI scan on day 5 ± 1. Q-space diffeomorphic reconstruction was performed using DSI Studio, and quantitative anisotropy (QA) was calculated. The CST was reconstructed based on QA. The dichotomized modified Rankin Scale score on day 90 (favorable outcome = 0–2) and Barthel Index (favorable recovery = 100 on day 90 or improvement between discharge and day 90 > 60%) were assessed. Thirty-three patients, median age 72 years (interquartile range (IQR) 64–83), 21 female (64%), 21 (64%) with lobar hemorrhage, median ICH volume on admission 15.0 (IQR 7.0–27.4) mL, were included. Sixteen patients (48%) had a favorable outcome and 24 (73%) had a favorable recovery. The mean number of ipsilesional reconstructed CST fiber pathways was higher in patients with favorable outcomes (153 (standard deviation (SD) 103) vs. 60 (SD 39), p = 0.003) and predicted outcome after adjustment (Exp(B) = 1.016 (95% CI = 1.002–1.030)). QA in the ipsilesional posterior limb of the internal capsule showed a trend towards an association with favorable outcome (Exp(B) = 1.194 (95% CI = 0.991–1.439 (adjusted))). The total (ipsilesional + contralesional) number of reconstructed fiber pathways was associated with favorable recovery (Exp(B) = 1.025 (95% CI = 1.003–1.047 (adjusted))). Quantitative tractography parameters assessed in the acute phase of ICH may represent a promising predictor of long-term outcome and recovery. This might facilitate prognostic evaluation and organization of rehabilitation.
CRIS-Team Scopus Importer:2020-10-02
Keywords: All rehabilitation; DWI; Intracerebral hemorrhage; MRI; Outcome research

Reactivation of HCMV during RT of the brain results in critical illness and early mortality - Frey, Benjamin; Goerig, Nicole; Becker, Ina; Donaubauer, Anna-Jasmina; Korn, Klaus; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Putz, Florian; Semrau, Sabine; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Snapshot CEST++: Advancing rapid whole-brain APTw-CEST MRI at 3 T - Sedykh, Maria; Liebig, Patrick; Herz, Kai; Fabian, Moritz; Mennecke, Angelika; Weinmüller, Simon; Schmidt, Manuel; Dörfler, Arnd; Zaiß, Moritz (NMR in Biomedicine, 2023)
APTw CEST MRI suffers from long preparation times and consequently long acquisition times ( 5 min). Recently, a consensus on the preparation module for clinical APTw CEST at 3 T was found in the community, and we present a fast whole-brain APTw CEST MRI sequence following this consensus preparation of pulsed RF irradiation of 2 s duration at 90% RF duty-cycle and a B1,rms of 2 μT. After optimization of the snapshot CEST approach for APTw imaging regarding flip angle, voxel size and frequency offset sampling, we extend it by undersampled GRE acquisition and compressed sensing reconstruction. This allows 2 mm isotropic whole-brain APTw imaging for clinical research at 3 T below 2 min. With this sequence, a fast snapshot APTw imaging method is now available for larger clinical studies of brain tumors.
CRIS-Team Scopus Importer:2023-08-04
Keywords: 3T CEST; APTw; brain tumor; compressed sensing; snapshot CEST

Standardized acquisition and post-processing of dynamic susceptibility contrast perfusion in patients with brain tumors, cerebrovascular disease and dementia: comparability of post-processing software - Schmidt, Manuel; Knott, Michael; Engelhorn, Tobias; Larsson, Elna Marie; Nguyen, Than; Essig, Marco; Dörfler, Arnd; Hölter, Philip (British Journal of Radiology, 2020)
OBJECTIVE: MR-perfusion post-processing still lacks standardization. This study evaluates the results of perfusion analysis with two established software solutions in a large series of patients with different diseases when a highly standardized processing workflow is ensured. METHODS: Multicenter data of 260 patients (80 with brain tumors, 124 with cerebrovascular disease and 56 with dementia examined with the same MR protocol) were analyzed. Raw data sets were processed with two software suites: Olea sphere and NordicICE. Group differences were analyzed with paired t-tests and one-way ANOVA. RESULTS: Perfusion metrics were significantly different for all examined diseases in the unaffected brain for both software suites [ratio cortex/white matter left hemisphere: mean transit time (MTT) 0.991 vs 0.847, p < 0.05; relative cerebral bloodflow (rBF) 3.23 vs 4.418, p < 0.001; relative cerebral bloodvolume (rBVc) 2.813 vs 3.884, p < 0.001; right hemisphere: MTT 1.079 vs 0.854, p < 0.05; rBF 3.262 vs 4.378, p < 0.001; rBVc 2.762 vs 3.935, p < 0.001)]. Perfusion results were also significantly different in patients with stroke (ratio cortex/white matter affected hemisphere: MTT 1.058 vs 0.784; p < 0.001), dementia (ratio cortex/white matter left hemisphere: rBVc 1.152 vs 1.795, p < 0.001; right hemisphere: rBVc 1.396 vs 1.662, p < 0.05) and brain tumors (ratio cortex/whole tumor rBVc: 0.778 vs 0.919, p < 0.001 and ratio cortex/tumor hotspot rBVc: 0.529 vs 0.512, p < 0.05). CONCLUSION: Despite a highly standardized workflow, parametric perfusion maps are depended on the chosen software. Radiologists should consider software related variances when using dynamic susceptibility contrast perfusion for clinical imaging and research. ADVANCES IN KNOWLEDGE: This multicenter study compared perfusion parameters calculated by two commercial dynamic susceptibility contrast perfusion post-processing software solutions in different central nervous system disorders with a large sample size and a highly standardized processing workflow. Despite, parametric perfusion maps are depended on the chosen software which impacts clinical imaging and research.
CRIS-Team Scopus Importer:2019-12-24

Stent-Assisted Coiling Using Leo+ Baby Stent: Immediate and Mid-Term Results - Lücking, Hannes; Struffert, Tobias; Gölitz, Philipp; Engelhorn, Tobias; Brandner, Sebastian; Kuramatsu, Joji; Lang, Stefan; Schmidt, Manuel; Dörfler, Arnd (Clinical Neuroradiology, 2020)
Background: Stent-assisted coiling is well-established for treatment of cerebral aneurysms. The technique enables treatment of wide-neck, bifurcation and recurrent aneurysms with high packing rates. While described in extenso for laser cut stents, the results of patients treated with the Leo+ Baby (Balt, Montmorency, France) braided microstent are presented. Material and Methods: Patients were included if treated with a Leo+ Baby and with digital subtraction angiography (DSA) follow-up available of at least 6 months. Data were evaluated for successful deployment, aneurysm occlusion according to the modified Raymond-Roy classification (MRRC), stent patency and procedure-related morbidity and mortality. Results: A total of 81 patients were included and Leo+ Baby deployment was successful in all cases. Coils were used in 80 cases. In 1 case 2 stents were used stent-in-stent without additional coiling. Initial aneurysm occlusion rates were MRRCi1 51.9%, MRRCi2 11.1%, MRRCi3a 24.7% and MRRCi3b 12.3%. Occlusion rates after 6 months were MRRC6m1 78.9%, MRRC6m2 3.9%, MRRC6m3a 6.6% and MRRC6m3b 10.5%. Procedure-related morbidity was 1 case of acute stent thrombosis successfully treated with tirofiban and 1 case with transient hemiparesis due to stent thrombosis after 4 months. There was 1 case of coil-associated subarachnoid hemorrhage (SAH) which caused prolonged hospitalization. No procedure-related mortality was observed. Conclusion: The results confirm that stent-assisted coiling with the Leo+ Baby stent is safe and efficient for treatment of wide neck or recurrent cerebral aneurysms. Spontaneous progressive aneurysm occlusion over 6 months supports the theory of considerable flow-modulating effects of Leo+ Baby.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Bifurcation aneurysm; Braided stent; Cerebral aneurysm; Coiling; Low profile stent

Surgical planning, histopathology findings and postoperative outcome in MR-negative extra-temporal epilepsy using intracranial EEG, functional imaging, magnetoencephalography, neuronavigation and intraoperative MRI. - Maslarova, Anna; Zhao, Yining; Rösch, Julie; Dörfler, Arnd; Coras, Roland; Blümcke, Ingmar; Lang, Johannes; Schmidt, Manuel; Hamer, Hajo; Reindl, Caroline; Welte, Tamara; Rampp, Stefan; et al. (Clinical Neurology and Neurosurgery, 2023)
OBJECTIVE: MRI-negative drug-resistant epilepsy presents a challenge when it comes to surgical planning, and surgical outcome is worse than in cases with an identified lesion. Although increasing implementation of more powerful MRI scanners and artificial intelligence has led to the detection of previously unrecognizable lesions, in some cases even postoperative pathological evaluation of electrographically epileptogenic zones shows no structural alterations. While in temporal lobe epilepsy a standardized resection approach can usually be performed, the surgical management of extra-temporal lesions is always individual. Here we present a strategy for treating patients with extra-temporal MRI-negative epilepsy focus and report our histological findings and patient outcome. METHODS: Patients undergoing epilepsy surgery in the Department of Neurosurgery at the University Hospital Erlangen between 2012 and 2020 were included in the study. Inclusion criteria were: (1) failure to identify a structural lesion on preoperative high-resolution 3 Tesla MRI with a standardized epilepsy protocol and (2) preoperative intracranial EEG (iEEG) diagnostics. RESULTS: We identified 8 patients corresponding to the inclusion criteria. Second look MRI analysis by an experienced neuroradiologist including the most recent analysis algorithm utilized in our clinic revealed a possible lesion in two patients. One of the patients with a clear focal cortical dysplasia (FCD) finding on a second look was excluded from further analysis. Of the other 7 patients, in one patient iEEG was performed with subdural electrodes, whereas the other 6 were evaluated with depth electrodes. MEG was performed preoperatively in all but one patient. An MEG focus was implemented in resection planning in 3 patients. FDG PET was performed in all, but only implemented in one patient. Histopathological evaluation revealed one non-lesional case, 4 cases of FCD and 2 cases with mild developmental malformation. All patients were free from permanent neurological deficits and presented with Engel 1A or 1B outcome on the last follow-up. CONCLUSION: We demonstrate that extra-temporal MRI-negative epilepsy can be treated successfully provided an extensive preoperative planning is performed. The most important diagnostic was stereo-EEG, whereas additional data from MEG was helpful and FDG PET was rarely useful in our cohort.
EVALuna2:522951

Symmetric tract-based spatial statistics of patients with left versus right mesial temporal lobe epilepsy with hippocampal sclerosis - Mennecke, Angelika; Rösch, Julie; Kasper, Burkhard; Schmidt, Manuel; Roessler, Karl; Coras, Roland; Hamer, Hajo; Dörfler, Arnd; Laun, Frederik Bernd (NeuroReport, 2018)
This study aims to investigate the diffusion metrics of left versus right temporal lobe epilepsy in a well-defined subgroup of patients with mesial temporal lobe epilepsy (mTLE) because of unilateral hippocampal sclerosis while taking into account interhemispheric differences. Eighteen patients with TLE [nine left temporal lobe epilepsy (LTLE) and nine right temporal lobe epilepsy (RTLE)] and a norm group of 36 nonepileptic individuals were scanned with a multiband accelerated diffusion tensor imaging protocol at 3T. The scalar diffusion tensor parameters fractional anisotropy (FA), mean diffusivity (MD), and radial diffusivity (RD) and, after projection on a symmetric skeleton, their hemispheric difference (dFA, dMD, and dRD) were analyzed using tract-based spatial statistics. In the cluster with significantly (P<0.008) different dFA, dMD, and dRD between right TLE and left TLE, the hemispheric difference in the mean scalar indices (dmFA, dmMD, and dmRD) was assessed and tested for differences using a one-way analysis of variance and for correlation with patient age, seizure onset, or duration of epilepsy using Pearson's correlation. Patients with LTLE showed lower dFA, higher dMD, and higher dRD (P<0.008) compared with patients with RTLE in a cluster including parts of the uncinated and inferior longitudinal fasciculus and the inferior fronto-occipital fasciculus. dmFA, dmMD, and dmRD differed significantly between groups (P<10, corrected) and showed no correlation with patient age, seizure onset, or duration of epilepsy. The exclusion of bilateral interindividual variance through the calculation of the hemispheric difference of the diffusion metrics by the symmetric variant of tract-based spatial statistics allows for a sensitive differentiation of LTLE and RTLE with unilateral hippocampal sclerosis.
EVALuna2:34910

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

The Segment Anything foundation model achieves favorable brain tumor auto-segmentation accuracy in MRI to support radiotherapy treatment planning - Putz, Florian; Beirami, Sogand; Schmidt, Manuel; May, Matthias; Grigo, Johanna; Weissmann, Thomas; Schubert, Philipp; Höfler, Daniel; Gomaa, Ahmed; Hassen, Ben Tkhayat; Lettmaier, Sebastian; Frey, Benjamin; et al. (Strahlentherapie und Onkologie, 2024)
Background: Promptable foundation auto-segmentation models like Segment Anything (SA, Meta AI, New York, USA) represent a novel class of universal deep learning auto-segmentation models that could be employed for interactive tumor auto-contouring in RT treatment planning. Methods: Segment Anything was evaluated in an interactive point-to-mask auto-segmentation task for glioma brain tumor auto-contouring in 16,744 transverse slices from 369 MRI datasets (BraTS 2020 dataset). Up to nine interactive point prompts were automatically placed per slice. Tumor boundaries were auto-segmented on contrast-enhanced T1w sequences. Out of the three auto-contours predicted by SA, accuracy was evaluated for the contour with the highest calculated IoU (Intersection over Union, “oracle mask,” simulating interactive model use with selection of the best tumor contour) and for the tumor contour with the highest model confidence (“suggested mask”). Results: Mean best IoU (mbIoU) using the best predicted tumor contour (oracle mask) in full MRI slices was 0.762 (IQR 0.713–0.917). The best 2D mask was achieved after a mean of 6.6 interactive point prompts (IQR 5–9). Segmentation accuracy was significantly better for high- compared to low-grade glioma cases (mbIoU 0.789 vs. 0.668). Accuracy was worse using the suggested mask (0.572). Stacking best tumor segmentations from transverse MRI slices, mean 3D Dice score for tumor auto-contouring was 0.872, which was improved to 0.919 by combining axial, sagittal, and coronal contours. Conclusion: The Segment Anything foundation segmentation model can achieve high accuracy for glioma brain tumor segmentation in MRI datasets. The results suggest that foundation segmentation models could facilitate RT treatment planning when properly integrated in a clinical application.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Artificial intelligence; Deep learning; Glioma; Interactive segmentation; Tumor auto-contouring

Transient Enlargement in Meningiomas Treated with Stereotactic Radiotherapy - Maksoud, Ziad; Schmidt, Manuel; Huang, Yixing; Rutzner, Sandra; Mansoorian, Sina; Weissmann, Thomas; Bert, Christoph; Distel, Luitpold; Semrau, Sabine; Lettmaier, Sebastian; Eyüpoglu, Ilker Yasin; Fietkau, Rainer; et al. (Cancers, 2022)
To investigate the occurrence of pseudoprogression/transient enlargement in meningiomas after stereotactic radiotherapy (RT) and to evaluate recently proposed volumetric RANO meningioma criteria for response assessment in the context of RT. Sixty-nine meningiomas (benign: 90%, atypical: 10%) received stereotactic RT from January 2005–May 2018. A total of 468 MRI studies were segmented longitudinally during a median follow-up of 42.3 months. Best response and local control were evaluated according to recently proposed volumetric RANO criteria. Transient enlargement was defined as volumetric increase ≥20% followed by a subsequent regression ≥20%. The mean best volumetric response was −23% change from baseline (range, −86% to +19%). According to RANO, the best volumetric response was SD in 81% (56/69), MR in 13% (9/69) and PR in 6% (4/69). Transient enlargement occurred in only 6% (4/69) post RT but would have represented 60% (3/5) of cases with progressive disease if not accounted for. Transient enlargement was characterized by a mean maximum volumetric increase of +181% (range, +24% to +389 %) with all cases occurring in the first year post-RT (range, 4.1–10.3 months). Transient enlargement was significantly more frequent with SRS or hypofractionation than with conventional fractionation (25% vs. 2%, p = 0.015). Five-year volumetric control was 97.8% if transient enlargement was recognized but 92.9% if not accounted for. Transient enlargement/pseudoprogression in the first year following SRS and hypofractionated RT represents an important differential diagnosis, especially because of the high volumetric control achieved with stereotactic RT. Meningioma enlargement during subsequent post-RT follow-up and after conventional fractionation should raise suspicion for tumor progression. <
Keywords: meningioma; volumetric analysis; segmentation; transient enlargement; pseudoprogression; stereotactic radiotherapy; radiosurgery; response assessment

Transient naming deficits associated with insular lesions in a patient with encephalitis - Marxreiter, Franz; Utz, Kathrin; Schlachetzki, Johannes; Seifert, Frank; Schmidt, Manuel; Dörfler, Arnd; Schwab, Stefan; Schenk, Thomas (Neurocase, 2019)
We describe a patient with acute herpes simplex encephalitis with left-hemispheric hippocampal, parahippocampal and insular lesions. Although prototypic language areas were unaffected, the patient suffered from an inability to name objects or animals displayed on pictures. This deficit was transient and gradually disappeared 8 weeks after the initial diagnosis. Our findings are in line with a previous report showing similar deficits in a patient with a comparable lesion pattern and support the hypothesis that left insular lesions can produce severe naming deficits. Using FDG-PET we ruled out that functional deactivation in classical language areas account for the observed naming deficits.
EVALuna2:204482

Ultra-High-Field 7 T Magnetic Resonance Imaging Including Dynamic and Static Contrast-Enhanced T1-Weighted Imaging Improves Detection of Secreting Pituitary Microadenomas - Eisenhut, Felix; Schlaffer, Sven-Martin; Hock, Stefan; Heynold, Elisabeth; Kremenevski, Natalia; Blümcke, Ingmar; Buchfelder, Michael; Dörfler, Arnd; Schmidt, Manuel (Investigative Radiology, 2022)
OBJECTIVE: A prospective preoperative evaluation of 7 T ultra-high-field magnetic resonance imaging (MRI) in patients with suspected pituitary microadenomas for both adenoma detection and intrasellar localization compared with 3 T MRI was carried out. MATERIALS AND METHODS: Patients underwent prospective preoperative standardized 3 and 7 T MRI. A distinct qualitative (lesion detection, intrasellar lesion location) and quantitative (lesion diameters, T1/T2 signal intensity ratio of the lesion to normal pituitary gland tissue) analysis was performed, along with an evaluation of image quality (IQ) regarding overall IQ, anatomical parameters, and artifacts; the findings of the qualitative analysis were compared with intraoperative findings and endocrinological outcomes. RESULTS: Sixteen patients (mean age, 43 ± 16 years; 13 women) with pituitary microadenomas were included. Using 7 T MRI allowed the detection of 15 microadenomas-3 more than 3 T MRI. In addition, 7 T MRI allowed more precise lesion localization with 93.75% (15/16) agreement with intraoperative findings, compared with 75% (12/16) agreement using 3 T MRI. Lesion diameters showed no significant difference between 3 and 7 T MRI. T1 and T2 signal intensity ratio between microadenomas and normal pituitary gland tissue were higher in 7 T MRI than in 3 T MRI. The overall IQ and the IQ of each anatomical parameter of 7 T MRI were rated higher than those of 3 T MRI. No significant differences in susceptibility or head motion artifacts were observed between 3 and 7 T MRI; however, 7 T MRI was more susceptible to pulsation artifacts. CONCLUSION: Ultra-high-field MRI surpasses 3 T MRI in pituitary microadenoma detection and enables more precise delineation with higher correlation with intraoperative findings. Thus, 7 T sellar imaging is a promising option-especially in previously magnetic resonance-negative patients with endocrinologically confirmed hormone oversecretion-and helps reduce the need for invasive diagnostics.
CRIS-Team Scopus Importer:2022-08-12

Ultra high-field SWI of the substantia nigra at 7T: reliability and consistency of the swallow-tail sign - Schmidt, Manuel; Engelhorn, Tobias; Marxreiter, Franz; Winkler, Jürgen; Lang, Stefan; Kloska, Stephan; Gölitz, Philipp; Dörfler, Arnd (BMC Neurology, 2017)
BACKGROUND: The loss of the swallow-tail sign of the substantia nigra has been proposed for diagnosis of Parkinson's disease. Aim was to evaluate, if the sign occurs consistently in healthy subjects and if it can be reliably detected with high-resolution 7T susceptibility weighted imaging (SWI). METHODS: Thirteen healthy adults received SWI at 7T. 3 neuroradiologists, who were blinded to patients' diagnosis, independently classified subjects regarding the swallow-tail sign to be present or absent. Accuracy, positive and negative predictive values (PPV and NPV) as well as inter- and intra-rater reliability and internal consistency were analyzed. RESULTS: The sign could be detected in 81% of the cases in consensus reading. Accuracy to detect the sign compared to the consensus was 100, 77 and 96% for the three readers with PPV reader 1/2/3 = 1/0.45/0.83 and NPV = 1/1/1. Inter-rater reliability was excellent (inter-class correlation coefficient = 0.844, alpha = 0.871). Intra-rater reliability was good to excellent (reader 1 R/L = 0.625/0.786; reader 2 = 0.7/0.64; reader 3 = 0.9/1). CONCLUSION: The swallow-tail sign can be reliably detected. However, our data suggest its occurrence is not consistent in healthy subjects. It may be possible that one reason is an individually variable molecular organization of nigrosome 1 so that it does not return a uniform signal in SWI.
EVALuna2:33135

Verbesserung der Deep Learning basierten Autodetektion von Hirnmetastasen durch Integration von MRT-Voraufnahmen - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2022)
Keywords: Deep learning; brain metastasis

"Virtual stent" - clinical evaluation and user experience of on-the-fly stent simulation in treatment of cerebral aneurysms - Lücking, Hannes; Birkhold, Annette; Hölter, Philip; Lang, Stefan; Gölitz, Philipp; Schmidt, Manuel; Mrochen, Anne; Brandner, Sebastian; Dörfler, Arnd (Interventional Neuroradiology, 2021)
Background Predicting final stent position can be challenging when treating cerebral aneurysms. Third-Party software proved helpful in selecting proper stents in treatment planning. Recent angiographic systems provide basic stent simulation capabilities integrated in the post-processing software to simulate stent position. Goal of this analysis was to evaluate the simulation process and correlation with definite stent position. Materials and Methods Thirty-three datasets with fusiform (n = 10) and saccular (n = 23) aneurysms, treated with stent or flow-diverter, were processed. A "virtual stent" of the same (nominal) size was simulated and its position was compared to the treatment result. Simulated length was rated in five grades (too short, shorter, equal, longer, too long), with regard to side-branches, anchoring zone etc. Simulation quality (centerline recognition/adherence to vessel margins) was rated in three grades (no, minor or major corrections required). Results Simulation was successful in 32/33 cases (97%), with one abortive attempt (3%). In 27/33 simulations (82%), there was no need for centerline refinement. Minor corrections were necessary in four and major corrections in two cases. Simulated nominal length was rated "equal" in 14/33 (42%) cases and "shorter" or "longer" - but within acceptable range - in each 9/33 (27%) cases. Conclusion Basic stent simulation tools available with genuine angiographic workplace software can provide good simulation capabilities without need for third-party equipment. They can facilitate treatment planning and help to avoid shortage of devices. Yet, lack of calculation of foreshortening in large vessel diameters leaves the user to rely on their experience to account for device-specific properties.
CRIS-Team WoS Importer:2021-11-12

Volumetric Regression in Brain Metastases After Stereotactic Radiotherapy: Time Course, Predictors, and Significance - Oft, Dominik; Schmidt, Manuel; Weissmann, Thomas; Roesch, Johannes; Mengling, Veit; Masitho, Siti; Bert, Christoph; Lettmaier, Sebastian; Frey, Benjamin; Distel, Luitpold; Fietkau, Rainer; Putz, Florian (Frontiers in Oncology, 2021)
Background: There is insufficient understanding of the natural course of volumetric regression in brain metastases after stereotactic radiotherapy (SRT) and optimal volumetric criteria for the assessment of response and progression in radiotherapy clinical trials for brain metastases are currently unknown. Methods: Volumetric analysis via whole-tumor segmentation in contrast-enhanced 1 mm³-isotropic T1-Mprage sequences before SRT and during follow-up. A total of 3,145 MRI studies of 419 brain metastases from 189 patients were segmented. Progression was defined using a volumetric extension of the RANO-BM criteria. A subset of 205 metastases without progression/radionecrosis during their entire follow-up of at least 3 months was used to study the natural course of volumetric regression after SRT. Predictors for volumetric regression were investigated. A second subset of 179 metastases was used to investigate the prognostic significance of volumetric response at 3 months (defined as ≥20% and ≥65% volume reduction, respectively) for subsequent local control. Results: Median relative metastasis volume post-SRT was 66.9% at 6 weeks, 38.6% at 3 months, 17.7% at 6 months, 2.7% at 12 months and 0.0% at 24 months. Radioresistant histology and FSRT vs. SRS were associated with reduced tumor regression for all time points. In multivariate linear regression, radiosensitive histology (p=0.006) was the only significant predictor for metastasis regression at 3 months. Volumetric regression ≥20% at 3 months post-SRT was the only significant prognostic factor for subsequent control in multivariate analysis (HR 0.63, p=0.023), whereas regression ≥65% was no significant predictor. Conclusions: Volumetric regression post-SRT does not occur at a constant rate but is most pronounced in the first 6 weeks to 3 months. Despite decreasing over time, volumetric regression continues beyond 6 months post-radiotherapy and may lead to complete resolution of controlled lesions by 24 months. Radioresistant histology is associated with slower regression. We found that a cutoff of ≥20% regression for the volumetric definition of response at 3 months post-SRT was predictive for subsequent control whereas the currently proposed definition of ≥65% was not. These results have implications for standardized volumetric criteria in future radiotherapy trials for brain metastases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: brain metastases; longitudinal analysis; MRI; stereotactic radiosurgery; stereotactic radiotherapy; volumetric analysis; volumetric regression

Voxel-wise lesion mapping of self-reported urinary incontinence in multiple sclerosis - Fröhlich, Katharina; Wang, Ruihao; Bobinger, Tobias; Schmidt, Manuel; Dörfler, Arnd; Nickel, Franziska; Hilz, Max-Josef; Lee, De-Hyung; Linker, Ralf A.; Seifert, Frank; Winder, Klemens (Neurourology and Urodynamics, 2019)
Aims Besides spinal lesions, urinary incontinence may be attributed to particular cerebral lesion sites in multiple sclerosis (MS) patients. We intended to determine the contribution of suprapontine lesions to urinary incontinence in MS using a voxel-wise lesion analysis. Methods In this retrospective study, we sought MS patients with documented urinary incontinence in a local database. We established a control group of MS-patients without documented urinary incontinence matched for gender, age, and disease severity. Patients with urinary incontinence due to local diseases of the urinary tract were excluded. The MS lesions were analyzed on T2-weighted magnetic resonance imaging scans (1.5 or 3T). After manual delineation and transformation into stereotaxic space, we determined the lesion overlap and compared the presence or absence of urinary incontinence voxel-wise between patients with and without lesions in a given voxel performing the Liebermeister test with 4000 permutations. Results A total of 56 patients with urinary incontinence and MS fulfilled the criteria and were included. The analysis yielded associations between urinary incontinence and MS in the frontal white matter, temporo-occipital, and parahippocampal regions. Conclusions Our voxel-wise analysis indicated associations between self-reported urinary incontinence and lesions in the left frontal white matter and right parahippocampal region. Thus, our data suggest that dysfunction of supraspinal bladder control due to cerebral lesions may contribute to the pathophysiology of urinary incontinence in MS.
CRIS-Team WoS Importer:2019-11-12

Whole-brain quantitative CEST MRI at 7T using parallel transmission methods and B1+ correction - Liebert, Andrzej; Tkotz, Katharina; Herrler, Jürgen; Linz, Peter; Mennecke, Angelika; German, Alex; Liebig, Patrick; Gumbrecht, Rene; Schmidt, Manuel; Dörfler, Arnd; Uder, Michael; Zaiß, Moritz; et al. (Magnetic Resonance in Medicine, 2021)
Purpose: To enable whole-brain quantitative CEST MRI at ultra-high magnetic field strengths (B0 ≥ 7T) within short acquisition times. Methods: Multiple interleaved mode saturation (MIMOSA) was combined with fast online-customized (FOCUS) parallel transmission (pTx) excitation pulses and (Formula presented.) correction to achieve homogenous whole-brain coverage. Examinations of 13 volunteers were performed on a 7T MRI system with 3 different types of pulse sequences: (1) saturation in circular polarized (CP) mode and CP mode readout, (2) MIMOSA and CP readout, and (3) MIMOSA and FOCUS readout. For comparison, the inverse magnetic transfer ratio metric for relayed nuclear Overhauser effect and amide proton transfer were calculated. To investigate the number of required acquisitions for a good (Formula presented.) correction, 4 volunteers were measured with 6 different B1 amplitudes. Finally, time point repeatability was investigated for 6 volunteers. Results: MIMOSA FOCUS sequence using (Formula presented.) correction, with both single and multiple points, reduced inhomogeneity of the CEST contrasts around the occipital lobe and cerebellum. Results indicate that the most stable inter-subject coefficient of variation was achieved using the MIMOSA FOCUS sequence. Time point repeatability of MIMOSA FOCUS with single-point (Formula presented.) correction showed a maximum coefficient of variation below 8% for 3 measurements in a single volunteer. Conclusion: A combination of MIMOSA FOCUS with a single-point (Formula presented.) correction can be used to achieve quantitative CEST measurements at ultra-high magnetic field strengths. Compared to previous (Formula presented.) correction methods, acquisition time can be reduced as additional scans required for (Formula presented.) correction can be omitted.
CRIS-Team Scopus Importer:2021-03-12
Keywords: 7T; chemical exchange saturation transfer; fast-online customized pulses; multiple interleaved mode saturation; parallel transmission; spiral non-selective trajectory